Organic / inorganic hybrid coating film and coating liquid
The organic/inorganic hybrid coating film with nanobubbles addresses the challenge of reducing coating material usage and weight increase by incorporating fine spherical spaces, ensuring flexibility and impact resistance, thereby maintaining fuel efficiency and acceleration performance.
Patent Information
- Application Number
- JP2024087592
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-05
- Filing Date
- 2024-05-30
- Publication Date
- 2024-12-17
AI Technical Summary
Coating liquids containing organic polysilazane are expensive, and reducing their application amount while maintaining a predetermined film thickness is necessary to avoid weight and cost increases, particularly in large surface area applications like automobiles, which can affect fuel efficiency and acceleration performance.
An organic/inorganic hybrid coating film with dispersed nanobubbles, formed using a coating liquid containing polysilazane, siloxane, and an inert organic solvent, reduces the amount of coating material needed by incorporating fine spherical spaces, maintaining flexibility and impact resistance while minimizing weight increase.
The hybrid coating film reduces the amount of coating material applied per unit area, minimizing weight increase and cost, while providing excellent impact resistance and corrosion resistance, thus preserving fuel efficiency and acceleration performance.
Smart Images

Figure 2024174835000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic / inorganic hybrid coating film that coats the surface of an article to be coated, and a coating liquid that forms the organic / inorganic hybrid coating film. [Background technology]
[0002] A coating liquid is disclosed that contains 20-60 wt% of organic polysilazane, 5-15 wt% of alkyl silicate condensate, and 0-80 wt% of organic solvent, and the content of methyl groups in the organic polysilazane is 50% or more (see Patent Document 1). In this coating liquid, the organic polysilazane reacts with moisture to form a coating layer of an inorganic-organic composite structure in which an organic functional group is bonded as a side chain to a part of the main chain by siloxane bond, and the alkyl silicate condensate acts as a crosslinking agent to form a crosslinked structure in the coating layer, thereby reducing the elastic modulus of the coating film and maintaining flexibility even if the film thickness is more than a certain level. Therefore, the coating film can follow the deformation of the article to be coated, the occurrence of cracks and peeling is prevented, and impact resistance and corrosion resistance can be ensured. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-14514 A Summary of the Invention [Problem to be solved by the invention]
[0004] Since the coating liquid containing organic polysilazane is expensive, it is desired to reduce the coating amount (coating amount) of the coating liquid on the surface (front and back) of the article to be coated and use the coating liquid inexpensively. However, since the coating film exerts its effect by coating the surface of the article to be coated with a predetermined film thickness, it is necessary to ensure a predetermined film thickness for the coating film after the coated coating liquid is hardened, and the coating amount cannot be reduced unconditionally. In addition, when the specific surface area of the article to be coated with the coating liquid is large and the coating liquid is coated on the entire article, the weight of the article including the coating film increases even though the film thickness of the coating film formed by hardening the coating liquid is small. For example, when the article to be coated with the coating liquid is an automobile, the weight of the automobile including the coating film increases, and the fuel efficiency and acceleration performance may decrease.
[0005] An object of the present invention is to provide an organic / inorganic hybrid coating film that can reduce the amount of coating on an article to be coated and can coat the surface of the article at low cost. Another object of the present invention is to provide an organic / inorganic hybrid coating film that can minimize the increase in weight of an article including an organic / inorganic hybrid coating film when the surface of the article to be coated is coated. Another object of the present invention is to provide a coating liquid that can reduce the amount of coating on an article to be coated and can be used at low cost. Another object of the present invention is to provide a coating liquid that can minimize the increase in weight of an article including an organic / inorganic hybrid coating film when the surface of the article to be coated is coated. [Means for solving the problem]
[0006] The first premise of the present invention for solving the above problems is an organic / inorganic hybrid coating film that contains a glass component in a hardened state and coats the surface of an article to be coated.
[0007] A first feature of the present invention in the first premise is that a large number of independent minute spherical spaces are dispersed and mixed inside the organic / inorganic hybrid coating film.
[0008] As an example of the present invention having the first characteristic, the spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The nanobubbles are dispersed and mixed at a specified concentration inside the organic / inorganic hybrid coating film.
[0009] As another example of the present invention having the first characteristic, the average particle diameter D of nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The nanobubbles are dispersed and mixed at a predetermined concentration inside the organic / inorganic hybrid coating film.
[0010] In another example of the present invention having the first characteristic, the content of nanobubbles in the organic / inorganic hybrid coating film is in the range of 10 to 95 vol. %.
[0011] In another example of the present invention having the first characteristic, the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these.
[0012] The second premise of the present invention for solving the above problems is a coating liquid that forms an organic / inorganic hybrid coating film that contains a glass component in a cured state on the surface of an article to be coated.
[0013] The second feature of the present invention in the second premise is that the coating liquid is made by mixing a liquid silicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent in a predetermined mixing ratio, or the coating liquid mainly consists of low molecular weight silane and consists of a silicon material, an alkyl silicate condensate, and an inert organic solvent, or the coating liquid mainly consists of low molecular weight silane has a large number of independent fine spherical spaces dispersed and mixed therein.
[0014] As an example of the present invention having the second characteristic, the spherical space is formed by nanobubbles, and the average particle diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.
[0015] As another example of the present invention having the second characteristic, the average particle diameter D of nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.
[0016] In another example of the present invention having the second characteristic, the content of nanobubbles in the coating liquid is in the range of 10 to 95 vol. %.
[0017] In another example of the present invention having the second characteristic, the blending ratio of the silicon material to the total mass of the coating liquid before nanobubbles are mixed in is in the range of 30 to 60 wt%, the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid before nanobubbles are mixed in is in the range of 10 to 15 wt%, the blending ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed in is in the range of 30 to 60 wt%, the viscosity of the coating liquid at 20°C into which the nanobubbles are dispersed is in the range of 0.98 to 1.008 mPa s, and the rising speed of the nanobubbles in the coating liquid at 20°C into which the nanobubbles are dispersed is in the range of 0·000015 to 0.00005 mm / min.
[0018] In another example of the present invention having the second characteristic, the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these. Effect of the Invention
[0019] According to the organic / inorganic hybrid coating film of the present invention, a large number of independent fine spherical spaces are dispersed (dispersed and dissolved) inside, so the ratio of the organic / inorganic hybrid coating film itself per unit area of the organic / inorganic hybrid coating film can be reduced by the large number of fine spherical spaces, and the amount of the organic / inorganic hybrid coating film itself is reduced when the surface (front and back) of the article to be coated is coated, so the amount of the organic / inorganic hybrid coating film coated on the article can be reduced, and the amount of the organic / inorganic hybrid coating film coated on the article can be reduced, and the surface of the article can be coated inexpensively with the organic / inorganic hybrid coating film because the amount of the coating is reduced compared to when the organic / inorganic hybrid coating film does not have spherical spaces dispersed (dispersed and dissolved). Since the mass per unit area of the organic / inorganic hybrid coating film is reduced compared to when the spherical spaces are not dispersed (dispersed and dissolved) in it, when the organic / inorganic hybrid coating film coats the surface of the article to be coated, the increase in the weight of the article including the organic / inorganic hybrid coating film can be minimized. For example, if the article coated with the organic / inorganic hybrid coating film is an automobile, the increase in weight of the automobile including the organic / inorganic hybrid coating film can be minimized, and the deterioration of the automobile's fuel efficiency and acceleration performance can be prevented. The organic / inorganic hybrid coating film contains a glass component, so it has excellent impact resistance and corrosion resistance, can maintain the coated state on the surface of the article for a long period of time, and can protect the surface of the article by the organic / inorganic coating film.
[0020] The spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The organic / inorganic hybrid coating film in which nanobubbles of the above are dispersed (dispersed and dissolved) at a specified concentration inside the organic / inorganic hybrid coating film has nanobubbles of the above with an average particle size of D 90By dispersing and mixing a large amount of nanobubbles with sizes of less than 1 μm at a predetermined concentration, the proportion of the organic / inorganic hybrid coating film itself per unit area of the organic / inorganic hybrid coating film can be reduced by the nanobubbles, which are ultrafine bubbles, and the amount of the organic / inorganic hybrid coating film itself coated when the surface of the article to be coated is reduced, and the amount of the organic / inorganic hybrid coating film coated on the article can be reduced, and the unit price of the organic / inorganic hybrid coating film per unit area of the surface of the article can be reduced by the reduced amount of coating compared to when nanobubbles are not dispersed and mixed in the organic / inorganic hybrid coating film, and the surface of the article can be coated inexpensively with the organic / inorganic hybrid coating film. Since the mass per unit area of the organic / inorganic hybrid coating film is reduced compared to when nanobubbles are not dispersed and mixed in it (dispersed and dissolved), when the organic / inorganic hybrid coating film coats the surface of the article to be coated, the increase in the weight of the article including the organic / inorganic hybrid coating film can be minimized. Even if the organic / inorganic hybrid coating film contains nanobubbles, which are ultra-fine bubbles, dispersed (dispersed and dissolved) in it, it contains glass components in a hardened state, so it has excellent impact resistance and corrosion resistance, can maintain the coating state on the surface of the article for a long period of time, and can reliably protect the surface of the article with the organic / inorganic hybrid coating film.
[0021] Average diameter of nanobubbles D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The organic / inorganic hybrid coating film, in which nanobubbles of the above are dispersed and mixed at a specified concentration inside the organic / inorganic hybrid coating film, has an average diameter of D 50By dispersing and mixing (dispersing and dissolving) a large amount of nanobubbles having a size in the range of 1 nm or more and less than 500 nm at a predetermined concentration, the proportion of the organic / inorganic hybrid coating film itself per unit area in the organic / inorganic hybrid coating film can be reduced by the nanobubbles, which are ultrafine bubbles. This makes it possible to reliably reduce the amount of the organic / inorganic hybrid coating film itself coated on the surface of the article to be coated, and by reducing the amount of coating, the unit price of the organic / inorganic hybrid coating film per unit area of the surface of the article decreases, making it possible to coat the surface of the article with the organic / inorganic hybrid coating film at low cost.
[0022] In an organic / inorganic hybrid coating film having a nanobubble content in the range of 10 to 95 vol.%, the content of the nanobubbles in the inorganic coating film in which the nanobubbles are dispersed and mixed is in the above range, so that ultrafine nanobubbles are dispersed and mixed in a large amount at a predetermined concentration inside the organic / inorganic hybrid coating film, and the proportion of the organic / inorganic hybrid coating film itself per unit area in the organic / inorganic hybrid coating film can be reliably reduced by the ultrafine nanobubbles, and the amount of the organic / inorganic hybrid coating film itself coated when the organic / inorganic hybrid coating film coats the surface of the article to be coated can be reliably reduced, and the reduced amount of coating reduces the unit price of the organic / inorganic hybrid coating film per unit area of the surface of the article, making it possible to coat the surface of the article with the organic / inorganic hybrid coating film at low cost.
[0023] The organic / inorganic hybrid coating film in which the gas that forms nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them, has a large number of nanobubbles (spherical spaces) of ultrafine bubbles made from the example gases or mixed gases of these gases dispersed and mixed (dispersed and dissolved) inside the organic / inorganic hybrid coating film, forming nanobubbles ( The use of the spherical space allows the ratio of the organic / inorganic hybrid coating film itself per unit area of the organic / inorganic hybrid coating film to be reduced, and the amount of the organic / inorganic hybrid coating film itself coated when the organic / inorganic hybrid coating film coats the surface of the article to be coated is reduced, making it possible to reduce the amount of the organic / inorganic hybrid coating film coated on the article, and the reduced amount of coating reduces the unit price of the organic / inorganic hybrid coating film per unit area of the surface of the article, making it possible to coat the surface of the article with the organic / inorganic hybrid coating film at low cost.
[0024] According to the coating liquid of the present invention, the coating liquid is made by mixing a liquid silicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent in a predetermined mixing ratio, or the coating liquid is mainly composed of low molecular weight silane, and a large number of independent fine spherical spaces are dispersed and mixed (dispersed and dissolved) therein. Therefore, the proportion of the coating liquid itself per unit volume of the coating liquid can be reduced by the large number of fine spherical spaces, and when the coating liquid that forms an organic / inorganic hybrid coating film is coated (applied) on the surface of the article to be coated, the coating amount (application amount) of the coating liquid itself is reduced, and the coating amount of the coating liquid on the article can be reduced. In addition, compared to the case where the spherical spaces are not dispersed and mixed in the coating liquid, the unit price of the coating liquid per unit area of the surface of the article is reduced by the reduction in the coating amount, and the coating liquid can be used inexpensively. The mass per unit volume of the coating liquid is reduced compared to when the spherical spaces are not dispersed (dispersed and dissolved) in the coating liquid, and therefore, when the coating liquid is applied to the surface of an article to be coated, the increase in the weight of the article including the organic / inorganic hybrid coating film formed (film-formed) from the coating liquid can be minimized. For example, when the article to be coated with the coating liquid is an automobile, the increase in the weight of the automobile including the organic / inorganic hybrid coating film made from the coating liquid can be minimized, and the decrease in fuel efficiency and acceleration performance of the automobile can be prevented. In the coating liquid, polysilazane, siloxane, and low molecular weight silane react with moisture to form a coating layer of an organic composite structure in which an organic functional group is bonded as a side chain to a part of the main chain by a siloxane bond, and the alkyl silicate condensate acts as a crosslinking agent to form a crosslinked structure in the coating layer, or the low molecular weight silane reacts with moisture to form a coating layer of an organic composite structure in which an organic functional group is bonded as a side chain to a part of the main chain by a siloxane bond, and therefore, the elastic modulus of the organic / inorganic hybrid coating film made from the coating liquid can be reduced, and flexibility can be maintained even when the film thickness is above a certain level.The coating liquid can make the organic / inorganic hybrid coating film made from the coating liquid conform to the deformation of the article to be coated, and can prevent the occurrence of cracks and peeling in the organic / inorganic hybrid coating film, and can form an organic / inorganic hybrid coating film having high impact resistance and high corrosion resistance on the surface of the article to be coated. Since the organic / inorganic hybrid coating film made from the coating liquid contains a glass component, the organic / inorganic hybrid inorganic coating film has excellent impact resistance and corrosion resistance, and can maintain the coated state on the surface of the article for a long period of time, and the organic / inorganic hybrid coating film can protect the surface of the article.
[0025] The spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The coating liquid in which nanobubbles of the above are dispersed (dispersed and dissolved) at a certain concentration has an average particle size of D 90By dispersing and mixing nanobubbles with sizes of less than 1 μm at a predetermined concentration, the proportion of the coating liquid itself per unit volume of the coating liquid can be reduced by the nanobubbles, and the amount of coating liquid itself when coated on the surface of the article to be coated can be reduced, and the amount of coating liquid applied to the article can be reduced. In addition, compared to when nanobubbles are not dispersed in the coating liquid, the reduced amount of coating reduces the unit price of the coating liquid per unit volume of the surface of the article, allowing the coating liquid for making the organic / inorganic hybrid coating film to be used at a low cost. Since the mass per unit volume of the coating liquid is reduced compared to when nanobubbles are not dispersed and mixed (dispersed and dissolved) in it, when the coating liquid is coated on the surface of the article to be coated, the increase in weight of the article including the organic / inorganic hybrid coating film formed from the coating liquid can be minimized. Even if the coating liquid contains nanobubbles, which are ultrafine bubbles, dispersed (dissolved) in the organic / inorganic hybrid coating film made from the coating liquid, the coating liquid hardens while still containing glass components. Therefore, the organic / inorganic hybrid coating film made from the coating liquid has excellent impact resistance and corrosion resistance and can maintain the coating state on the surface of the article for a long period of time, and the organic / inorganic hybrid coating film can reliably protect the surface of the article.
[0026] Average diameter of nanobubbles D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50In a coating liquid in which the nanobubbles are dispersed and mixed (dispersed and dissolved) at a predetermined concentration in the coating liquid, the nanobubbles are negatively charged, so that the nanobubbles dispersed and mixed in the coating liquid repel each other and do not bond (coalesce) with each other, and it is possible to prevent the nanobubbles from bonding together and becoming giant bubbles, and it is possible to maintain the dispersed and mixed state of the ultrafine bubbles in the coating liquid that forms the organic / inorganic hybrid coating film. Since the ultrafine bubbles are dispersed and mixed (dispersed and dissolved) in the coating liquid without bonding together, the nanobubbles are unlikely to volatilize from the coating liquid, and the nanobubbles can be allowed to remain in the coating liquid for a long period of time. The coating liquid contains nanobubbles having an average particle size D in the above range. 50 Since a large amount of nanobubbles are dispersed and mixed (dispersed and dissolved) at a predetermined concentration, the proportion of the coating liquid itself per unit volume in the coating liquid can be reduced by the use of nanobubbles, which are ultrafine bubbles, and the amount of coating liquid itself can be reliably reduced when coating the surface of an article to be coated with the coating liquid that creates an organic / inorganic hybrid coating film.
[0027] A coating liquid having a nanobubble content in the range of 10 to 95 vol. % has a nanobubble content in the above range, and a large amount of ultrafine nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration, and the proportion of the coating liquid itself per unit volume in the coating liquid can be reduced by the ultrafine nanobubbles, and the coating amount of the coating liquid itself can be reliably reduced when coating the coating liquid on the surface of an article to be coated. Furthermore, the reduced coating amount reduces the unit price of the coating liquid per unit area of the surface of the article, and the coating liquid that forms the organic / inorganic hybrid coating film can be used inexpensively.
[0028] The blending ratio of the silicon material to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 wt%, the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid before nanobubbles are mixed is in the range of 10 to 15 wt%, the blending ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 wt%, the viscosity of the coating liquid at 20°C in which the nanobubbles are dispersed and mixed is in the range of 0.98 to 1.008 mPa s, and the rising speed of the nanobubbles in the coating liquid at 20°C in which the nanobubbles are dispersed and mixed is 0.0000 In the coating liquid in the range of 15 to 0.00005 mm / min, the viscosity of the coating liquid in which the nanobubbles are dispersed (dispersed and dissolved) at 20°C is within the above range, and the rising speed of the nanobubbles in the coating liquid at 20°C in which the nanobubbles are dispersed is within the above range, so that the nanobubbles are less likely to volatilize from the coating liquid, the nanobubbles can be made to remain in the coating liquid for a long period of time, and the amount of the coating liquid itself can be reliably reduced when coating the coating liquid for forming an organic / inorganic hybrid coating film on the surface of the article to be coated. Since the coating liquid has a blending ratio of the silicon material within the above range, the organic / inorganic hybrid coating film made from the coating liquid is formed to a predetermined thickness, and an organic / inorganic hybrid coating film having high impact resistance and high corrosion resistance can be formed on the surface of the article to be coated. Since the coating liquid has a blending ratio of the alkyl silicate condensate within the above range, the formation speed of the organic / inorganic hybrid coating film made from the coating liquid can be accurately controlled.
[0029] In a coating liquid in which the gas forming nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them, a large number of nanobubbles (spherical spaces) of ultrafine bubbles made from the example gases or mixed gases of these gases are dispersed and mixed (dispersed and dissolved) inside the coating liquid, and the proportion of the coating liquid itself per unit volume of the coating liquid can be reduced by the ultrafine nanobubbles (spherical spaces). When the coating liquid that forms an organic / inorganic hybrid coating film is coated on the surface of an article to be coated, the coating amount of the coating liquid itself is reduced, and the coating amount of the coating liquid on the article can be reduced. At the same time, the unit price of the coating liquid per unit area of the surface of the article is reduced by the reduction in the coating amount, and the coating liquid can be used inexpensively. [Brief description of the drawings]
[0030] [Figure 1] FIG. 2 is a configuration diagram showing an example of a nanobubble generating device that mixes nanobubbles 14 into a coating liquid. [Diagram 2] Cross-sectional diagrams explaining in chronological order the mechanism by which an organic / inorganic hybrid coating film is formed from a coating liquid on the surface of an article coated with the coating liquid. [Diagram 3] FIG. 1 is a cross-sectional view showing an example of an organic / inorganic hybrid coating film whose main component is a low molecular weight silane. [Figure 4] An image showing an example of the structure of an organic / inorganic hybrid coating film. [Diagram 5] A diagram showing an image of nanobubbles dispersed and mixed inside an organic / inorganic hybrid coating film. [Figure 6] FIG. 1 shows the correlation between the thickness of an organic / inorganic hybrid coating film and its impact resistance and corrosion resistance. [Figure 7] FIG. 2 shows the blend ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquids of Samples A to E and the organic / inorganic hybrid coating films made from the coating liquids of Samples A to E. [Figure 8] FIG. 13 shows the porosity, total number of nanobubbles, and nanobubble diameter of the coating liquids of Samples F to H and the organic / inorganic hybrid coating films made from the coating liquids of Samples F to H. [Figure 9] FIG. 2 shows the blend ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquids of Samples I to K and the organic / inorganic hybrid coating films made from the coating liquids of Samples I to K. [Figure 10] Graph showing the evaluation of flexibility, impact resistance, and corrosion resistance of organic / inorganic hybrid coating films made from the coating liquids of samples A to K. [Figure 11] FIG. 1 shows the evaluation of flexibility, impact resistance, and corrosion resistance of organic / inorganic hybrid coating films made from the coating solutions of Samples I to K. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The coating liquid and the organic / inorganic hybrid coating film according to the present invention will be described in detail with reference to the attached drawings. FIG. 1 is a configuration diagram showing an example of a nanobubble generator 15 for mixing nanobubbles 14 into a coating liquid 10, and (a) to (c) of FIG. 2 are cross-sectional views for explaining in a time series the mechanism by which an organic / inorganic hybrid coating film 13 is formed from the coating liquid 10 on a surface 12 (front and back) of an article 11 coated (applied) with the coating liquid 10. FIG. 3 is a cross-sectional view showing an example of an organic / inorganic hybrid coating film 13 containing low-molecular-weight silane as a main component, and FIG. 4 is an image diagram showing an example of the structure of the organic / inorganic hybrid coating film 13. FIG. 5 is a diagram illustrating an image of nanobubbles 14 dispersed (dissolved) in the organic / inorganic hybrid coating film 13, and FIG. 6 is a diagram illustrating the correlation between the thickness of the organic / inorganic hybrid coating film 13 and the impact resistance and corrosion resistance. In FIG. 5, the nanobubbles 14 are illustrated as spherical images that can be seen with the naked eye, but in reality the nanobubbles 14 cannot be seen with the naked eye.
[0032] (Coating Liquid 10) The coating liquid 10 is coated (applied) on a surface 12 (front and back) of an article 11 to be coated. The hardened coating liquid 10 forms an organic / inorganic hybrid coating film 13 that covers the surface 12 of the article 11. The raw materials for the coating liquid 10 include a liquid organosilicon material (silicon material) made of at least one of polysilazane (inorganic polysilazane, organic polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent. Alternatively, a low molecular weight silane is used. Inside the coating liquid 10 (in the coating liquid 10), particles having an average particle size D 90 Nanobubbles 14 (ultrafine bubbles) (numerous independent tiny spherical spaces) with sizes less than 1 μm are dispersed and mixed (dispersed and dissolved) at a specified concentration.
[0033] Either one of polysilazane and siloxane (polymeric silane) may be used, or a mixture of both may be used. An organosilicon material, an alkylsilicate condensate, and an inert organic solvent are mixed and stirred at a predetermined ratio to produce the coating liquid 10. In the coating liquid 10, an organosilicon material consisting of at least one of polysilazane and siloxane, and an alkylsilicate condensate are diluted with an inert organic solvent. The inorganic polysilazane used is Si-N perhydropolysilazane. As the polysilazane, Si-CN organopolysilazane, Si-C polycarbosilane, SiC-O, Si-BCN, and Si-Ti-N can also be used. Organopolysiloxane can also be used. As the organic polysilazane, modified polysilazanes such as methylpolysilazane, dimethylpolysilazane, phenylpolysilazane, vinylpolysilazane, etc. can also be used. Also usable is a crosslinked polysilazane that is chemically crosslinked with a compound such as a hydrocarbon compound having a reactive group such as a hydroxyl group, a vinyl group, an amino group, or a silyl group that chemically reacts with polysilazane to form a crosslinked structure, a cyclic saturated hydrocarbon compound, a cyclic unsaturated hydrocarbon compound, a saturated heterocyclic compound, an unsaturated heterocyclic compound, or a silicone compound. In addition, polyborosilazane, inorganic silazane high polymers or modified polysilazanes, copolymerized silazanes, low-temperature ceramicized polysilazanes obtained by adding or incorporating a catalytic compound to polysilazane to promote ceramicization, silicon alkoxide-added polysilazanes, glycidol-added polysilazanes, acetylacetonato complex-added polysilazanes, metal carboxylate-added polysilazanes, and polysilazane compositions obtained by adding amines and / or acids to the above-mentioned various polysilazanes or modified products can also be used. The polysilazane may be one type of single polysilazane, a mixture of two or more types of polysilazanes selected from various polysilazanes, or a polysilazane copolymer consisting of two or more types of polysilazane structures, and contains at least one hydrogen atom directly bonded to a silicon atom in one molecule. The polysilazane forming the coating liquid 10 has a weight average molecular weight in the range of 100 to 100,000,000, preferably 1,000 to 1,000,000, and more preferably 2,000 to 500,000, from the viewpoints of solubility in a solvent and workability during application. If the weight average molecular weight is 100 or more, the volatility is low, and the polysilazane itself volatilizes during the volatilization of the solvent and the curing process, which may deteriorate the film quality of the coating film. The inorganic polysilazane is represented by the general formula (Chemical Formula 1). [ka] Inorganic polysilazanes include linear structures having structural units, have a molecular weight of 690 to 2,000, and contain 3 to 10 SiH groups in one molecule. 3 groups and have element ratios by weight of Si: 59-61, N: 31-34, and H: 6.5-7.5 as determined by chemical analysis; and perhydropolysilazane having a polystyrene-equivalent average molecular weight in the range of 3,000 to 20,000. Perhydropolysilazane contains chain and cyclic portions in its molecule and is represented by the following chemical formula (Chemical Formula 2). [ka] An example of the structure of perhydropolysilazane is represented by the following chemical formula (Chemical Formula 3). [ka] Another example of the perhydropolysilazane compound group is represented by the following general formula (Chemical Formula 4), which has a Si-N bond and a functional group (R 1 ~R 3 ), and -(SiR 1 R 2 -NR 3)-units, and has a functional group R that is directly bonded to Si. 1 ,R 2 At least one of the above is an organic polymer formed from an organic functional group such as an alkyl group having carbon (C). [ka] Perhydropolysilazane is a functional group (R 1 ~R 3 ) is a methyl group (CH 3 ) content is 50% or more. Perhydropolysilazane is a compound that contains one type of -(SiR 1 R 2 -NR 3 )-units, as well as polymers formed from functional groups (R 1 ~R 3 ) with different compositions 1 R 2 -NR 3 The perhydropolysilazane may be a polymer formed from R 1 , R 2 , R 3 represents a hydrogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an aryl group, or a group other than these groups in which the group directly bonded to silicon is carbon, an alkylsilyl group, an alkylamino group, or an alkoxy group. 1 , R 2 , R 3 At least one of is a hydrogen atom. As an example, perhydropolysilazane (A) is represented by the following general formula (Chemical Formula 5): -(SiH(CH 3 )-NH)- unit, -(Si(CH 3 )2-NH)- unit, -(SiR 1 (CH 3 )-NR 3 )-units. 1 (CH 3)-NR 3 The functional group R1 in the -unit is H or CH 3 and the functional group R3 directly bonded to N is an organic functional group that promotes the reaction. By including perhydropolysilazane (A) in the coating liquid 13, the reaction after the coating liquid 10 is coated on the surface 12 of the article 11 is promoted, and an organic / inorganic hybrid coating film 13 can be formed on the surface 12 of the article 11 at an early stage. [ka] Another example of perhydropolysilazane (B) is -(SiH(CH) represented by the following general formula (Chemical Formula 6). 3 )-NH)- unit, -(SiR 1 (CH 3 )-NH)- units, and 1 (CH 3 Functional group R of the -NH)- unit 1 is an organic functional group that realizes high heat resistance. By including perhydropolysilazane (B) in the coating liquid 10, the heat resistance of the organic / inorganic hybrid coating film 13 that covers the surface 12 of the article 11 can be improved. [ka] The perhydropolysilazane contained in the coating liquid 10 may be a mixture of multiple types of perhydropolysilazanes having different polymer structures. For example, perhydropolysilazane may be a mixture of perhydropolysilazane (A) and perhydropolysilazane (B). According to a mixing experiment of these perhydropolysilazane (A) and perhydropolysilazane (B), it was confirmed that a mixture of 50 mass% perhydropolysilazane (A) and 50 mass% perhydropolysilazane (B) exhibited rust prevention properties equal to or greater than that of perhydropolysilazane (A) alone, and also reduced the curing time (time to generate organic / inorganic hybrid coating film 13) compared to perhydropolysilazane (B) alone. Organopolysilazane is represented by the general formula (4) above,1 and R 2 has a hydrogen atom, R 3 has an organic group at -(R 2 SiHNH)- as a repeating unit, and has a cyclic structure with a degree of polymerization of 3 to 5, polysilazane, (R 3 SiHNH) x 〔(R 2 SiH) 1.5 N〕 1-X (0.4 < X < 1), polysilazane having both a chain structure and a cyclic structure in the molecule represented by the chemical formula, in the above general formula (Chemical Formula 4), R 1 has a hydrogen atom, R 2 , R 3 has an organic group, polysilazane, R 1 and R 2 has an organic group, R 3 has a hydrogen atom at -(R 1 R 2 SiNR 3 )- as a repeating unit, and there is polysilazane mainly having a cyclic structure with a degree of polymerization of 3 to 5. For example, organopolysilazane having a crosslinked structure other than the above general formula (Chemical Formula 4) in the molecule is represented by the following general formula (Chemical Formula 7).
Chemical Formula
Chemical Formula
[0034] The siloxane contained in the coating liquid 10 may be any one of a chain siloxane having a chain skeleton and a cyclic siloxane having a cyclic skeleton, or a mixture of two or more of them. As the cyclic siloxane, hexamethylcyclotrisiloxane (C 6 H 18 O 3 S 4 ), Octamethylcyclotetrasiloxane (C 6 H 24 O 4 S 4 ), Decamethylcyclopentasiloxane (C 10 H 30 O 5 S 5 ) or a mixture of two or more of them can be used. The number average molecular weight of polysilazane and siloxane is in the range of 3000 to 150000 g / mol.
[0035] The alkyl silicate condensate is one selected from tetramethyl orthosilicate, tetraethyl orthosilicate, tetra-n-propyl orthosilicate, tetra-i-propyl orthosilicate, tetra-n-butyl orthosilicate, tetra-sec-butyl orthosilicate, methyl polysilicate, and ethyl polysilicate, or a condensate (mixture) of two or more of them. The inert organic solvent is inert to polysilazane, siloxane, and alkyl silicate condensates, and is selected from dibutyl ether, turpentine oil, benzene, and toluene.
[0036] Since the number average molecular weight of the polysilazane (perhydropolysilazane, organopolysilazane, organopolysiloxane, etc.) or siloxane in the coating liquid 10 is within the above range, the coating liquid 10 containing the polysilazane and / or siloxane can maintain a predetermined viscosity, and an organic / inorganic hybrid coating film 13 can be formed from the coating liquid 10. Since the coating liquid 10 is coated on the surface 12 of the article 11 to be coated while maintaining a predetermined viscosity, even if the coating liquid 10 is coated on the surface 12 of the article 11 on which minute holes or meshes are formed, the coating liquid 10 does not permeate into the inside of the article 11, and an organic / inorganic hybrid coating film 13 with a substantially uniform thickness can be formed on the surface 12 of the article 11.
[0037] In the coating liquid 10, the mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 mass%, the mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid before nanobubbles are mixed is in the range of 10 to 15 mass%, and the mixing ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 mass%. If the mixing ratio of the organosilicon material (polysilazane, siloxane) is less than 30 mass%, the content of the organosilicon material is low, and it is not possible to form an organic / inorganic hybrid coating film 13 of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the article 11. If the mixing ratio of the organosilicon material (polysilazane, siloxane) exceeds 60 mass%, the viscosity of the coating liquid 10 increases, and nanobubbles 14 described later cannot be dispersed and mixed (dispersed and dissolved) in the coating liquid 10 at a predetermined concentration. Since the mixing ratio of the organosilicon material (polysilazane, siloxane) to the total mass of the coating liquid 10 before the nanobubbles are mixed in falls within the above-mentioned range, by using the coating liquid 10 after the nanobubbles have been mixed in, it is possible to produce an organic / inorganic hybrid coating film 13 of an appropriate thickness that has excellent flexibility, impact resistance, and corrosion resistance, and in which the nanobubbles 14 are dispersed and mixed (dissolved) at a predetermined density.
[0038] If the blending ratio of the alkyl silicate condensate is less than 10 mass%, the alkyl silicate condensate has a weak effect as a crosslinking agent, and a sufficient crosslinked structure is not formed in the organic / inorganic hybrid coating film 13. If the blending ratio of the alkyl silicate condensate exceeds 15 mass%, an unnecessary crosslinked structure is formed in the organic / inorganic hybrid coating film 13, and the flexibility of the organic / inorganic hybrid coating film 13 becomes greater than necessary. Since the blending ratio of the alkyl silicate condensate to the total mass before the nanobubbles are mixed in is within the above range, the coating liquid 10 after the nanobubbles are mixed in can be used to create an organic / inorganic hybrid coating film 13 having an appropriate crosslinked structure and appropriate flexibility, and in which the nanobubbles are dispersed and mixed at a predetermined density.
[0039] If the blending ratio of the inert organic solvent is less than 30% by mass, the viscosity of the coating liquid 10 becomes high, and the nanobubbles 14 cannot be dispersed (dissolved) at a predetermined concentration inside the coating liquid 10. If the blending ratio of the inert organic solvent exceeds 60% by mass, the viscosity of the coating liquid 10 becomes lower than necessary, and an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance and a predetermined thickness cannot be formed on the surface 12 of the article 11. Since the blending ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed in is within the above range, the coating liquid 10 after nanobubbles are mixed in can be used to create an organic / inorganic hybrid coating film 13 having an appropriate viscosity in which the nanobubbles 14 are dispersed (dissolved) at a predetermined density and which has excellent flexibility, impact resistance, and corrosion resistance.
[0040] The coating liquid 10 contains 30 to 60 mass % of the organosilicon material (polysilazane and / or siloxane) and 10 to 15 mass % of the alkylsilicate condensate relative to the total mass of the coating liquid before nanobubbles are mixed in, so that the formation rate of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 can be appropriately controlled. Specifically, the hydrolysis of the alkylsilicate condensate proceeds faster than the condensation of the polysilazane and / or siloxane, so that some water (H 2 O) is consumed first, it is possible to retard the progress of the condensation reaction of polysilazane and / or siloxane, and to control the rate of formation of the organic / inorganic hybrid coating film 13. In addition, since the hydrolysis of the alkyl silicate condensate occurs first, it is possible to reliably form a crosslinked structure in the organic / inorganic hybrid coating film 13 and impart flexibility to it.
[0041] In addition, since the organic solvent is selected from dibutyl ether, turpentine oil, benzene, and toluene, which are inactive to polysilazane, siloxane, and alkyl silicate condensates, the condensation reaction of polysilazane and / or siloxane does not progress rapidly, and the rate of formation of the organic / inorganic hybrid coating film 13 can be appropriately controlled. The coating liquid 10 capable of controlling the rate of formation of the organic / inorganic hybrid coating film 13 allows easy coating of the surface 12 of the article 11.
[0042] Low molecular weight silanes are made from chlorosilanes, and contain multiple organic functional groups and hydrolyzable alkoxy groups in one molecule, forming an amorphous glass coating through dehydration crosslinking. Low molecular weight silanes have multifunctional groups that strongly bond with organic substances, and hydrolyzable alkoxy groups that strongly bond with inorganic substances. Low molecular weight silanes can be made into low molecular weight liquids by 100% functionalization (high concentration of vitrification components and solvent-free possible). Furthermore, they do not contain volatile silanol groups, so they have high storage and stability. The hardening speed of low molecular weight silanes can be adjusted, and they can be hand-painted. Low molecular weight silanes can be hand-painted even without solvent (highest concentration of vitrification components) because they are low molecular weight. Furthermore, because they are low molecular weight, they have high wettability and leveling properties, and the glossy aesthetic quality of the finished product is stable.
[0043] (Nanobubble mixing device 15) As shown in Fig. 1, an example of the nanobubble mixing device 15 is composed of a coating liquid storage tank 16 having a predetermined volume, a gas supply tank 17, a water supply pump 18 and an air supply pump 19, a static fluid mixer 20 (nanobubble generator), a coating liquid storage tank 21 having a predetermined volume and storing the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed, a cooling device (not shown), and a controller (not shown). The nanobubble mixing device 15 is supplied with power from a power source (not shown). The coating liquid storage tank 16 stores the coating liquid 10 (the coating liquid 10 before the nanobubbles 14 are dispersed and mixed) obtained by mixing and stirring a liquid organosilicon material consisting of at least one of the above-mentioned polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent at a predetermined mixing ratio, or stores the coating liquid 10 mainly composed of a liquid low-molecular-weight silane (the coating liquid 10 before the nanobubbles 14 are dispersed and mixed).
[0044] A level gauge (not shown) is installed in the coating liquid storage tank 16. The level gauge is connected to the controller via a signal line, measures the level (storage amount) of the coating liquid 10 stored in the coating liquid storage tank 16, and transmits the measured level to the controller. The coating liquid storage tank 16 is connected to a water supply pump 18 via a water supply pipe 22 (water supply pipe). Although not shown, a flow meter, a check valve, and a water supply solenoid valve are installed in the water supply pipe 22. The flow meter is connected to the controller via a signal line, measures the flow rate of the coating liquid 10 flowing through the water supply pipe 22, and transmits the measured flow rate to the controller. A control unit of the water supply solenoid valve is connected to the controller via a signal line, and its start / stop (open / close) is controlled by the controller.
[0045] The gas supply tank 17 contains a gas to be dispersed and mixed into the coating liquid 10 at a predetermined pressure. The gas to be dispersed and mixed into the coating liquid 10 may be any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them. The gas supply tank 17 is connected to a mixing pipe 24 (mixing pipe) via an air supply pipe 23 (air supply pipe). Although not shown, a barometer, a check valve, and an air supply solenoid valve are installed in the air supply pipe 23. The barometer is connected to a controller via a signal line, measures the air pressure of the gas contained in the gas supply tank 17, and transmits the measured air pressure to the controller. The control unit of the air supply solenoid valve is connected to the controller via a signal line, and its on / off (opening / closing) is controlled by the controller. An air supply pump 19 is installed in the air supply pipe 23. The control unit of the air supply pump 19 is connected to the controller via a signal line. The on / off and output of the air supply pump 19 are controlled by the controller.
[0046] The water supply pump 18 is installed in a water supply pipe 22, and its control unit is connected to the controller via a signal line. The start / stop and output of the water supply pump 18 are controlled by the controller. The water supply pump 18 is connected to a static fluid mixer 20 via a mixing pipe 24. The static fluid mixer 20 is connected to a coating liquid storage tank 21 of a predetermined volume via a supply pipe 25. A level meter (not shown) is installed in the coating liquid storage tank 21. The level meter is connected to the controller via a signal line, measures the level (storage volume) of the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed and stored in the coating liquid storage tank 21, and transmits the measured level to the controller.
[0047] The static fluid mixer 20 (nanobubble generator) is formed of a cylindrical unit 26 having an inlet and an outlet, and a plurality of honeycomb structure elements (agitation blades) (not shown) arranged inside the cylindrical unit 26. The honeycomb structure elements are arranged in a state of being connected in series inside the cylindrical unit 26. The static fluid mixer 20 (nanobubble generator) passes the coating liquid 10 and gas through the inside of the honeycomb structure element by centrifugal force generated by high-speed rotation, and generates nanobubbles 14 by ultra-finely dividing the gas into nano-level particles, while uniformly mixing (dissolving) the generated nanobubbles 14 into the coating liquid 10, thereby producing the coating liquid 10 in which the nanobubbles 14 are uniformly dispersed and mixed (dispersed and dissolved) throughout. In the static fluid mixer 20, the coating liquid 10 and the gas pass through the inside of the honeycomb structure element many times, thereby proceeding with ultra-finely dividing the gas (to nano-level) and mixing (dissolving) the ultra-finely divided gas into the coating liquid 10. The cooling device cools the cylindrical unit 26 of the static fluid mixer 20 to a set temperature by circulating a refrigerant (e.g., hydrofluorocarbon). The control unit of the cooling device is connected to the controller via a signal line. The start / stop and output of the cooling device are controlled by the controller.
[0048] The controller is a physical computer that has a central processing unit (CPU or MPU) and memory (main memory and cache memory), runs on an independent operating system (OS), and is equipped with a large-capacity storage area. Input devices such as a keyboard and mouse, and output devices such as a display and printer are connected to the controller via interfaces. The central processing unit of the controller starts a nanobubble mixing application stored in the memory based on the control of the operating system (OS), and performs a mixing operation to disperse and mix (disperse and dissolve) nanobubbles 14 into the coating liquid 10 according to the application.
[0049] When the switch of the nanobubble mixing device 15 is turned on, a mixing operation of mixing nanobubbles 14 into the coating liquid 10 stored in the coating liquid storage tank 16 is started. A predetermined amount of the coating liquid 10 is poured into the coating liquid storage tank 16, and gas (any of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them) is stored at a predetermined pressure in the gas supply tank 17. When the switch of the nanobubble mixing device 15 is turned on, the controller sends a water supply signal to the control unit of the water supply pump 18, sends an air supply signal to the control unit of the air supply pump 19, and sends a cooling signal to the control unit of the cooling device. Furthermore, the controller sends an open signal to the control section of the water supply solenoid valve, sends an open signal to the control section of the air supply solenoid valve, and sends measurement signals to the level meter, flow meter, and barometer.
[0050] The control unit of the water supply pump 18 that has received the water supply signal starts the water supply pump 18 at a predetermined output (set output), and the control unit of the air supply pump 19 that has received the air supply signal starts the air supply pump 19 at a predetermined output (set output). The control unit of the cooling device that has received the cooling signal starts the cooling device at a predetermined output (set output). The control unit of the water supply solenoid valve that has received the open signal opens the water supply solenoid valve, and the control unit of the air supply solenoid valve that has received the open signal opens the air supply solenoid valve. The level meter that has received the measurement signal starts measuring the level of the coating liquid 10 stored in the coating liquid storage tank 16, and the flow meter that has received the measurement signal starts measuring the flow rate of the coating liquid 10 flowing through the water supply pipe 22. The barometer that has received the measurement signal starts measuring the air pressure of the gas flowing through the air supply pipe 23.
[0051] The coating liquid 10 stored in the coating liquid storage tank 16 is forcibly supplied from the coating liquid storage tank 16 to the static fluid mixer 20 by starting the water supply pump 18 (coating liquid water supply step). The coating liquid 10 flows from the water supply pipe 22 through the water supply pump 18 into the mixing pipe 24, and flows into the static fluid mixer 20 through the mixing pipe 24. The gas stored in the gas supply tank 17 is forcibly supplied from the gas supply tank 17 to the static fluid mixer 20 by starting the air supply pump 19 (gas supply step). The gas flows from the air supply pipe 23 through the air supply pump 19 into the mixing pipe 24, is mixed with the coating liquid 10 in the mixing pipe 24, and then flows into the static fluid mixer 24 together with the coating liquid 10. In the mixing pipe 24, the coating liquid supplied by the water supply pump 18 and the gas supplied by the air supply pump 19 are mixed to produce a gas-mixed coating liquid (mixing process). The gas-mixed coating liquid flows into the static fluid mixer 20.
[0052] The controller receives the measured level measured by the level meter of the coating liquid storage tank 16 and outputs (displays) a water injection message on the display when the measured level drops to the water injection level. The water injection message informs the user of the need to inject the coating liquid 10 into the coating liquid storage tank 16. The controller receives the measured flow rate measured by the flow meter and adjusts the output of the water supply pump 18 so that the measured flow rate becomes the target flow rate. The controller receives the measured air pressure measured by the barometer and adjusts the output of the air supply pump 19 so that the measured air pressure becomes the target air pressure.
[0053] The cooling device continuously cools the cylindrical unit 26 of the static fluid mixer 20 using a refrigerant while the nanobubble mixing device 15 is running (cooling process). The cooling device maintains the temperature of the cylindrical unit 26 at a set temperature (for example, 10 to 20°C). In the static fluid mixer 20, the gas-mixed coating liquid 10 mixed with gas flows in from its inlet, and the gas-mixed coating liquid 10 becomes a continuous phase fluid and a dispersed phase fluid by multiple honeycomb structure elements (agitating blades), and the continuous phase and dispersed phase fluids of the gas-mixed coating liquid 10 flow while meandering through the honeycomb structure elements. The fluid (gas) as the dispersed phase is atomized by the shear force received at that time, and a finely atomized mixed fluid is generated.
[0054] Next, the flow of the generated finely divided mixed fluid is rectified, and then the rectified finely divided mixed fluid flows while meandering through the honeycomb structure element arranged on the downstream side, and the finely divided mixed fluid (gas) as the dispersed phase is further refined by the shear force received at that time. Finally, the gas mixed into the coating liquid 10 is ultra-refined to the nano level, and nano-level bubbles (nanobubbles) are dispersed and mixed (dispersed and dissolved) in the coating liquid 10, and particles with an average particle diameter D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm to 500 nm, more preferably, the average particle size D 50A nanobubble-containing coating liquid 10 is produced in which nanobubbles 14 (numerous independent tiny spherical spaces) having a size in the range of 1 nm or more and less than 300 nm are uniformly dispersed and mixed in at a predetermined concentration (nanobubble-containing coating liquid production process).
[0055] When the nanobubbles 14 are mixed into the coating liquid, the temperature of the nanobubble-containing coating liquid 10 in the cylindrical unit 26 in which the nanobubbles are dispersed and mixed rises due to friction between the coating liquid and the nanobubbles 14. However, the cooling device cools the cylindrical unit 26, so that the temperature of the nanobubble-containing coating liquid 10 in the cylindrical unit 26 is maintained at 10 to 20°C. The coating liquid 10 in which the nanobubbles 14 are dispersed and mixed (dispersed and dissolved) is contained in the coating liquid storage tank 21 through the supply pipe 25. The controller receives the measurement level measured by the level meter of the coating liquid storage tank 21 and outputs (displays) the measurement level on a display. The amount of the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed can be known from the measurement level outputted on the display.
[0056] Regarding the method of dispersing and mixing the nanobubbles 10 into the coating liquid 10 (nanobubble generation method), any of the methods involving the flow of the coating liquid 10, such as a swirling liquid flow method, a static mixer method, an ejector type, a Venturi type, or a pressurized dissolution type, may be used, or any of the methods not involving the flow of the coating liquid 10, such as a fine hole type, a rotation type, an ultrasonic type, a steam condensation type, or an electrolysis type, may be used.
[0057] The coating liquid 10 is a coating liquid 10 in which a liquid organosilicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent are mixed in a predetermined mixing ratio, or in which low-molecular-weight silane is the main component. Nanobubbles 14 (a large number of independent minute spherical spaces) are dispersed and mixed (dispersed and dissolved) in the coating liquid 10, so that the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 (the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed (dispersed and dissolved)) is reduced by the nanobubbles 14 (spherical spaces). This reduces the amount of coating (application amount) of the coating liquid 10 itself when the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 dispersed therein (dispersed and dissolved therein) is coated on the surface 12 of the article 11 to be coated, thereby reducing the amount of coating of the coating liquid 10 on the article 11. Furthermore, compared to a case in which the nanobubbles 14 are not dispersed in the coating liquid 10, the reduced amount of coating reduces the unit cost of the coating liquid 10 per unit area of the surface 12 of the article 11, and the coating liquid 10 can be coated (used) inexpensively.
[0058] The coating liquid 10 has a reduced mass per unit volume compared to when the nanobubbles 14 (spherical spaces) are not dispersed (dispersed and dissolved) in it, and therefore when the coating liquid 10 is applied to the surface 12 of the article 11 to be coated, it is possible to minimize the increase in weight of the article 11 including the organic / inorganic hybrid coating film 13 formed from the coating liquid 10. For example, when the article 11 to be coated with the coating liquid 10 is an automobile, it is possible to minimize the increase in weight of the automobile including the organic / inorganic hybrid coating film 13 made from the coating liquid 10, and it is possible to prevent a decrease in the fuel efficiency and acceleration performance of the automobile.
[0059] The nanobubbles 14 dispersed and mixed inside the coating liquid 10 have an average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, preferably, the average particle size D50 is in the range of 1 nm or more and less than 300 nm. The maximum particle size distribution of the nanobubbles 14 inside the coating liquid 10 is in the range of 50 nm or more and less than 500 nm, preferably in the range of 10 nm or more and less than 300 nm. The content of the nanobubbles 14 in the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, more preferably in the range of 50 to 90 vol.%. The total number of nanobubbles 14 per ml of the coating liquid 10 is 10 7 ~10 12 The particle size and particle size distribution of the nanobubbles 14 in the coating liquid 10, the porosity, and the total number of nanobubbles 14 were measured by nanoparticle tracking analysis (NTA). With nanoparticle tracking analysis, the particle size distribution, particle number concentration, and aggregation state of the nanobubbles 14 in the coating liquid 10 can be measured with high resolution.
[0060] In the nanoparticle tracking analysis method, the coating liquid 10 in which nanobubbles 14 are dispersed is placed in a sample chamber, and the sample chamber is irradiated with laser light. In the nanoparticle tracking analysis method, the 90° scattered light of each nanobubble 14 irradiated with laser light is detected by a highly sensitive CMOS camera. The Brownian motion of the detected particles is observed as the movement of bright spots on the camera image and tracked. The diffusion coefficient is obtained by tracking this movement, and the particle size of the nanobubbles 14 is determined by the Stokes-Einstein equation. The particle distribution (concentration) is calculated by calculating the number of nanobubbles 14 per ml from all particle counts within the camera field of view, which has a known volume, and the content of nanobubbles in the coating liquid 10 and the total number of nanobubbles 14 per ml of the coating liquid 10 are calculated. In the nanoparticle tracking analysis method, the zeta potential of the particles is determined by measuring the electrophoretic mobility when a constant voltage is applied to the cell.
[0061] The coating liquid 10 in which the nanobubbles 14 are dispersed and mixed by the nanobubble mixing device 15 is mixed with hydrogen ions H + Concentration and hydroxide ion OH -The properties of the nanobubbles 14 with respect to acidity and baseness, which are approximately equal in concentration, are approximately neutral or alkaline. The nanobubbles 14 dispersed and mixed inside the coating liquid 10 are mixed into the coating liquid 10 in the form of spheres having high internal bubble pressure, and are negatively charged.
[0062] The nanobubbles 14 in the coating liquid 10 have a diameter of less than 1 μm and a Reynolds number Re of approximately 1, forming spherical bubbles. The shape (sphere) of the nanobubbles 14 was observed using an atom probe field ion microscope (APFIM). The atom probe field ion microscope is a field ion microscope (FIM) equipped with a time-of-flight mass analyzer, and individual nanobubbles 14 are observed using the field ion microscope and identified by time-of-flight mass analysis. The shape (sphere) of the nanobubbles 14 in the coating liquid 10 is reproduced with a resolution of approximately nanoscale level by displaying it three-dimensionally on a graphic workstation.
[0063] The nanobubbles 14 mixed in the coating liquid 10 rise slowly inside the coating liquid 10. The rising speed of the nanobubbles 14 depends on the liquid properties of the coating liquid 10, but in water, the nanobubbles have a diameter of about 100 μm and a Reynolds number Re of approximately 1, forming spherical bubbles. The rising speed U of a spherical bubble with a diameter d is given by the Stokes equation: U=pgd 2 / 18μ, where p is the liquid density, g is the gravitational acceleration, and μ is the liquid viscosity.
[0064] The nanobubbles 14 mixed (dissolved) inside the coating liquid 10 have a high internal bubble pressure (self-pressurizing effect). The internal bubble pressure is higher than the pressure around the bubble by ΔP according to the Young-Laplace equation: ΔP = 4σ / d due to the influence of surface tension σ. The relationship between the diameter d of the bubble in the coating liquid 10 and the internal bubble pressure is that the smaller the bubble, the higher the internal bubble pressure (3.87 "atm" for 1 μm, 29.7 "atm" for 100 nm, surface tension σ of water: 72.8 mN / m (20°C), pressure around the bubble is 1 "atm"). Therefore, when the bubble shrinks, the partial pressure of the dissolved gas component, that is, the driving force for dissolution, increases, and by reducing the gas to nano size, the gas becomes more easily dissolved in the coating liquid 10, and a large amount of nanobubbles 14 dissolves in the coating liquid 10.
[0065] The nanobubbles 14 mixed (dissolved) inside the coating liquid 10 have a large gas-liquid interface area. The gas-liquid interface area per unit volume, A / V, is expressed by the formula: A / V=6d. A / V increases as the bubble diameter d decreases, and this ratio contributes greatly to the amount of gas mixed (dissolved) in the coating liquid 10. The amount of gas mixed (dissolved) in the nanobubbles 14 is extremely large. The mass transfer rate N (mol / s) of the bubbles into the coating liquid 10 is expressed by the formula: N=K G A(pp*), where KG is the gas-phase reference overall mass transfer coefficient (mol / m 2 sPa”, A is the surface area of the bubble [m 2 ], p is the partial pressure of the dissolved component in the bubble (Pa), and p* is the partial pressure of the gas phase in equilibrium with the dissolved component in the liquid phase (Pa).
[0066] When the gas in the bubbles dissolves (mixes) into the coating liquid 10, the overall mass transfer resistance is 1 / K L or 1 / K G H is the liquid phase resistance 1 / k L and gas phase resistance 1 / k G As a sum of H and Ohm's law of electrical resistance: 1 / K L =1 / K G H=1 / k L +1 / kG H. Here, K L is the liquid phase reference overall mass transfer coefficient, H is Henry's constant (p = H C ), formula: 1 / K L =1 / K G H=1 / k L +1 / k G If the gas-side mass transfer resistance 1 / kGH can be substantially ignored at H, the liquid-phase reference overall mass transfer coefficient KL and the liquid-side mass transfer coefficient kL become substantially equal.
[0067] For a spherical bubble, the Reynolds number Re<1 and the rising speed are as follows: U=pgd 2 Liquid phase mass transfer coefficient k when expressed as / 18μ L is the formula: L =D L / d[l+(1+dU / D L ) 1 / 3 ] where D L is the diffusion coefficient of the gas in the liquid phase, d is the bubble diameter, and U is the rising speed of the bubble. For example, the formula: L =D L +dl+[(1+dU / D L ) 1 / 3 ] by the bubble diameter and the liquid-side mass transfer coefficient k of the MB-water system L When the bubble diameter d is 100 μm, k L is 1.817 10 -4 "m / s", k when bubble diameter d is 10 μm L is 5.37·10 -4 "m / s", k when bubble diameter d is 1 μm L is 5.20·10 -3 The diffusion coefficient D of oxygen in the coating liquid 10 is L is 2.60 10 -9 "m 2 / s" was used.
[0068] k for the bubble diameter d L Using the value of N = K and the bubble internal pressure (atm) for the bubble diameter d, the formula is: G The mass transfer rate N was calculated using A(pp*), and rearranged. As a result, when the bubble diameter d was 10 μm, the upward velocity U was 3.26·10 -3"m / min", pressure difference ΔP is 2.91·10 4 , bubble number ratio is 1.0·10 6 , area ratio is 100, mass transfer rate ratio is 6.15·10 4 "mol / s" and 1.0·10 8 "mol / mm", and when the bubble diameter d is 100 nm, the rising speed U is 3.15·10 -7 "m / min", pressure difference ΔP is 2.91·10 6 , bubble number ratio is 1.0·10 12 , area ratio is 1.0 10 4 , mass transfer rate ratio is 5.95 10 10 "mol / s" and 1.0·10 18 "mol / mm".
[0069] If a spherical bubble with a diameter of 1 mm is divided into bubbles with a diameter of 10 μm, the number of bubbles will be 10 6 If a spherical bubble with a diameter of 1 mm is divided into bubbles with a diameter of 100 nm, the number of bubbles will increase by 10. 12 The surface area of a bubble with a diameter of 1 mm is increased to 10 4 Therefore, if the mass transfer rate (dissolution rate) per unit time of a bubble with a diameter of 1 mm is 1, then the mass transfer rate (dissolution rate) of a bubble with a diameter of 10 μm is 6·10 4 The mass transfer rate (dissolution rate) per unit time for a bubble with a diameter of 1 mm is 1, and for a bubble with a diameter of 100 nm, the mass transfer rate (dissolution rate) is 6·10 10 In this way, the mass transfer rate (dissolution rate) in the coating liquid 10 increases rapidly due to the increase in the surface area and the partial pressure inside the bubbles and the decrease in the rate of rise as a result of the bubbles becoming nano-sized.
[0070] The surface potential of the nanobubbles 14 was measured using electrophoresis experimental equipment. The negatively charged nanobubbles 14 generated in the container move in a zigzag pattern by switching the electric field direction of the electrodes introduced into the electrophoresis cell (thickness 1 mm, height 23.0 mm, width 75.0 mm) every 1 second. The bubble diameter was calculated using the Stokes equation by measuring the upward speed, and the zeta potential of the bubbles was calculated using the Smoluchowski equation: ζ=μu / ε by measuring the horizontal speed. Here, ζ is the zeta potential "V", μ is the viscosity of the coating liquid 10 "kg / ms", and u is the mobility of the bubbles "m 2 / sV”, ε is the dielectric constant of the coating liquid 10 “s 2 C 2 / kgm 3 "
[0071] The nanobubbles 14 are negatively charged at -30 to -40 "mV" regardless of their particle size (bubble diameter). The cluster structure of the coating liquid 10 is formed from the molecules of the coating liquid 10 and ionized + ions and - ions, and + ions and - ions tend to fit into the structure, but - ions in particular tend to accumulate at the interface, resulting in a negative charge. The negative charge of the nanobubbles 14 causes the nanobubbles 14 in the coating liquid 10 to repel each other, and the nanobubbles 14 do not bond (unite) with each other due to electrostatic repulsion.
[0072] Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 are negatively charged, the nanobubbles 14 dispersed and mixed in the coating liquid 10 repel each other and do not bond (coalesce) with each other, which prevents the nanobubbles 14 from bonding together and becoming large bubbles, and the ultrafine nanobubbles 14 can be maintained in a dispersed state in the coating liquid 10. Since the nanobubbles 14 do not bond (coalesce) with each other in the coating liquid 10 and the ultrafine nanobubbles 14 are dispersed and mixed (dispersed and dissolved) in the coating liquid 10, the nanobubbles 14 are less likely to volatilize from the coating liquid 10, and the nanobubbles 14 can remain in the coating liquid 10 for a long period of time.
[0073] In the coating liquid 10, the nanobubbles 14 are not in a columnar state but in a spherical state having a high internal bubble pressure and are dispersed (dissolved) in a large amount at a predetermined concentration in the coating liquid 10. 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 A large amount of nanobubbles 14 having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed in the coating liquid 10 at a predetermined concentration (high concentration), the content of the nanobubbles 14 in the coating liquid 10 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 95 vol.%, and the total number of nanobubbles 14 per ml of the coating liquid 10 is 10 7 ~10 12 Since the nanobubbles 14 are in the range of nanobubbles per 1 ml, the proportion of the coating liquid 10 itself per unit volume in the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 mixed (dissolved) therein) can be reduced by the use of the ultrafine bubbles 14, and the coating amount of the coating liquid 10 itself can be reliably reduced when the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 mixed (dissolved) therein) is coated on the surface 12 of the article 11 to be coated.
[0074] The coating liquid 10 after the nanobubbles 14 are dispersed and mixed therein has a viscosity in the range of 0.98 to 1.008 mPa·s at 20°C. Furthermore, the rising speed of the nanobubbles 14 in the coating liquid 10 having the above viscosity range at 20°C after the nanobubbles 14 are dispersed and mixed therein is in the range of 0·000015 to 0.00005 mm / min. The nanobubbles 14 have an extremely small volume, so that their rising speed in the coating liquid 10 is extremely slow. If the rising speed of the nanobubbles 14 in the coating liquid 10 exceeds 0.00005 mm / min, it is difficult to keep the nanobubbles 14 in the coating liquid 10 for a long period of time, and the nanobubbles 14 may volatilize from the coating liquid 10 within the target residence time.
[0075] The forces acting on the nanobubbles 14 inside the coating liquid 10 include buoyancy and drag. Buoyancy is proportional to the volume of the nanobubbles 14 (proportional to the cube of the radius of the nanobubbles 14). Drag is proportional to the cross-sectional area of the nanobubbles 14 (proportional to the square of the radius of the nanobubbles 14) and proportional to the square of the rising speed of the nanobubbles 14. Specifically, if the radius of the nanobubbles 14 is r, the density of the coating liquid 10 is ρ, the gravitational acceleration is g, the viscosity of the coating liquid 10 is η, and the moving speed of the nanobubbles 14 is u, then the buoyancy acting on the nanobubbles 14 (ignoring the density of the nanobubbles) is expressed by Archimedes' principle as follows: F=4πr 3 It is expressed by ρg / 3.
[0076] The resistance force acting on the nanobubbles 14 is expressed by the formula (2): F = 6πηru according to Stokes' theorem. From the formulas (1) and (2), the moving speed u of the nanobubbles 14 inside the coating liquid 10 is expressed by the formula (3): u = (2 / 9)r 2 It is expressed by ρg / η. The rising speed of the nanobubbles 14 in the coating liquid 10 was calculated from formula (3). As is clear from formula (3), the larger the radius r (particle size) of the nanobubbles 14, the higher the moving speed u of the nanobubbles 14 in the coating liquid 10.
[0077] When the radius r of the nanobubble 14 under 1 atmospheric pressure is a, the radius r and the water depth h are calculated by the following formula (4): r = a × {101325 / (ρgh + 101325)} 1 / 3 As is clear from formulas (3) and (4), the nanobubbles 14 have larger particle sizes and rise faster as the water depth of the coating liquid 10 becomes shallower.
[0078] As a hypothesis, nanobubbles 14 with a diameter of less than 1.0 μm have their solubility reduced by the salting-out phenomenon, and remain stable for a long period of time inside the coating liquid 10. If nanobubbles 14 continue to exist stably for a long period of time due to the salting-out phenomenon, there would be no coating liquid 10 containing nanobubbles 14 with a pH close to 7, but there are cases in which stable nanobubbles 14 exist even in neutral liquids.
[0079] Generally, when nanobubbles 14 are mixed with larger microbubbles, the nanobubbles 14 rise to the surface due to the influence of the latter larger microbubbles, or are affected by cavitation destruction due to external pressure, shortening the lifespan of the nanobubbles 14. However, when nanobubbles 14 are generated in the nanobubble mixing device 15, large microbubbles with diameters of 1.0 μm or more are not generated, so the lifespan of the generated nanobubbles 14 can be made longer.
[0080] (Item 11 (substrate) to be coated) The article 11 to be coated with the coating liquid 10 is a metal molded product, a plastic molded product, a glass molded product, a rubber molded product, a leather molded product, a wood molded product, a paper molded product, a woven fabric molded product, or a nonwoven fabric molded product. The shapes of these molded products are arbitrary (free). Materials for metal molded products include iron, aluminum, duralumin, stainless steel, copper, gold, silver, titanium, nickel, alloys, etc. Metal molded products made of these materials have various shapes such as plates, rods, and other three-dimensional shapes. Materials for plastic molded products include known thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyamide (nylon), vinyl chloride resin, acrylic resin, silicone resin, fluororesin, polyimide resin, and polysulfone resin, and thermosetting resins such as epoxy resin, melamine resin, phenolic resin, and unsaturated polyester resin. Plastic molded products made of these materials have various shapes such as films, sheets, plates, and other three-dimensional shapes.
[0081] (Method of Coating (Applying) Coating Liquid 10) The coating liquid 10 is coated or sprayed on the surface 12 of the article 11 to be coated, and chemically reacts with moisture to form (form) an organic / inorganic hybrid coating film 13, which is a single or multiple layer ultra-thin film. The organic / inorganic hybrid coating film 13 is formed as a film having a thickness in the range of 5 nm to 1 μm, preferably in the range of 50 nm to 500 nm. There is no particular limitation on the method of coating the surface 12 of the various articles 11 with the coating liquid 10, and the surface 12 is coated by a coating method suitable for the shape of the article 11 to be coated. For example, the surface 12 is coated by a spray method, a dipping method, a brush coating method, a roll coating method, a gravure coating method, a flexography method, an inkjet method, or the like. There is no particular limitation on the amount of coating (application amount) of the coating liquid 10, and the amount of coating is determined according to the surface performance required for the article 11 to be coated. Generally, the amount of coating is 0.1 to 20 g / m in terms of solid content. 2 The coating amount is 0.1g / m 2 If the coating amount is less than 20 g / m, the organic / inorganic hybrid coating film 13 having the desired properties is not formed. 2 If it exceeds this value, the thickness of the organic / inorganic hybrid coating film 13 increases more than necessary, and the organic / inorganic hybrid coating film 13 loses its flexibility.
[0082] In addition, as a pretreatment step prior to the coating step of the coating liquid 10, water such as purified water (H 2 O) may be sprayed onto the surface 12 of the article 11 to adhere water to the surface 12 of the article 11. In this manner, a chemical reaction between the water adhered to the surface 12 of the article 11 and the components contained in the coating liquid 10 is promoted, and an organic / inorganic hybrid coating film 13 can be rapidly formed on the surface 12 of the article 11, and a strong organic / inorganic hybrid coating film 13 can be formed on the surface 12 of the article 11.
[0083] Furthermore, a coating liquid containing inorganic polysilazane as a main component can be coated as a primer on the surface 12 of the article 11 as a pretreatment step prior to the coating step of the coating liquid 10. For example, when a solution of inorganic polysilazane (1 wt % solution) is coated and then the coating liquid 10 is coated, the rust prevention (durability) of the organic / inorganic hybrid coating film 13 is improved compared to when only the coating liquid 10 is simply coated. (Mechanism of formation of organic / inorganic hybrid coating film 13) Next, a mechanism for forming the organic / inorganic hybrid coating film 13 on the surface 12 of the article 11 will be described. After the surface 12 of the article 11 is coated with the coating liquid 10 by the coating process, the surface 12 of the article 11 is left at room temperature (normal temperature) without being heated. Alternatively, after the surface 12 of the article 11 is coated with the coating liquid 10, the surface 12 of the article 11 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after the surface 12 of the article 11 is coated with the coating liquid 10, the surface 12 of the article 11 is irradiated with ultraviolet rays while being irradiated with infrared rays to heat the temperature of the surface 12 of the article 11 to less than 400°C.
[0084] As shown in FIG. 2(a), a small amount of moisture 27 (water droplets) is attached to the surface 12 of the article 11 due to condensation or humidity in the air (water (H 2 When the surface 12 of the article 11 is coated with the coating liquid 10 in a thin film form by a coating process, the -(SiR 1 R 2 -NR 3 )-unit components and / or -(SiR 1 R 2 -NR 3 )-unit component is moisture in the air (H 20), an organic composite structure (-(Si(CH) in an example of a structural image of an organic / inorganic hybrid coating film 13 shown in FIG. 3) in which an organic functional group is bonded as a side chain to a part of the main chain by a siloxane bond (Si-O-Si) is formed on the surface 12 of the article 11. 3 ) 2 -O-Si(CH 3 ) 2 The above chemical reaction produces an organic / inorganic hybrid coating film 13 having a cation exchange unit (C1,C2,C3,C4,C5,C6,C7,C8,C9,C10,C11,C12,C13,C14,C15,C16,C17,C18,C19,C20,C21,C22,C30,C23,C24,C31,C25,C32, 3 ,H 2 These gases do not remain on the surface 12 of the article 11 but evaporate (emit) into the atmosphere.
[0085] As shown in FIG. 2(b), the coating liquid 10 containing polysilazane and / or siloxane undergoes a chemical reaction (deammonia cross-linking) with moisture contained in the air in the surface layer 28 in contact with the air, whereby gases such as hydrogen and ammonia, which are by-products of the organic / inorganic hybrid coating film 13, volatilize from the surface 12 to the outside air, and a coating layer 29 is formed (generated) on the surface 12 side of the organic / inorganic hybrid coating film 13.
[0086] The coating liquid 10 coated on the surface 12 of the article 11 undergoes a chemical reaction (deammonia cross-linking) with the moisture 27 (water droplets) attached to the surface 12 or with the hydroxyl groups -OH (see Figure 3) present as terminal ends on the surface 12 in the back layer 30 in contact with the surface 12 of the article 11, causing gases such as hydrogen and ammonia to rise within the coating layer and volatilize from the surface 12 to the outside air, and a coating layer 31 on the back side of the organic / inorganic hybrid coating film 13 is formed (generated).
[0087] First, the coating layers 11, 12 (vitrified (inorganized) portion and organic portion) are generated in the surface layer 28 and the back layer 30 of the coating liquid 10. Next, the coating layers 29, 31 (vitrified (inorganized) portion and organic portion) are formed and expanded from the surface layer 28 side toward the back layer 30 side, and the coating layers 29, 31 (vitrified (inorganized) portion and organic portion) are expanded from the back layer 30 side toward the surface layer 28 side, so that the coating layer 21 (vitrified (inorganized) portion and organic portion) of the intermediate layer 33 is formed (generated) in sequence, and finally, the organic / inorganic hybrid coating film 13 is formed (generated) on the surface layer 28 in contact with the outside air, the back layer 30 in contact with the surface 12 of the article 11, and the intermediate layer 33 between the surface layer 28 and the back layer 30.
[0088] The organic / inorganic hybrid coating film 13 made of polysilazane and / or siloxane is composed of a glass coating layer (amorphous glass coating layer) and an organic coating layer. The organic / inorganic hybrid coating film 13 is mainly composed of SiO2 generated by reacting polysilazane and / or siloxane, and thus a coating layer that spreads easily in a plane and has high density and high hardness (vertical hardness of about 6H to 9H) is formed, forming an ultra-thin film structure at the nano level.
[0089] The low molecular weight silane contained in the coating liquid 10 forms an organic / inorganic hybrid coating film 13 (amorphous glass coating film) by dehydration crosslinking. The organic / inorganic hybrid coating film 13 made from the low molecular weight silane is formed of a glass coating layer (amorphous glass coating layer) and an organic coating layer.
[0090] The organic / inorganic hybrid coating film 13 is formed as an ultra-thin film at the nano-level because the coating liquid 10 contains polysilazane and / or siloxane or low molecular weight silane. The film thickness is in the range of 5 nm to 1 μm, preferably in the range of 50 nm to 500 nm. Although the organic / inorganic hybrid coating film 13 is a coating film mainly composed of SiO2, it has excellent flexibility, and in combination with the anchor effect of the anchor parts 36, it will not peel off even if the surface 12 of the article 11 is a material that causes deformation such as a cloth material, and the coating state of the organic / inorganic hybrid coating film 13 can be maintained by following the deformation of the surface 12 of the article 11.
[0091] As shown in FIG. 5, the organic / inorganic hybrid coating film 13 formed by hardening the coating liquid 10 on the surface 12 of the article 11 has an average particle diameter D 90 However, nanobubbles 14 smaller than 1 μm remain as they are and are trapped in the organic / inorganic hybrid coating film 13, and the nanobubbles 14 are dispersed (dissolved) at a predetermined concentration. The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 are spheres with high internal bubble pressure, similar to the state in which they were dispersed and mixed in the coating liquid 10, and the average particle diameter D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm to 500 nm, more preferably, the average particle size D 50 is in the range of 1 nm or more and less than 300 nm. The maximum particle size distribution of the nanobubbles 14 inside the organic / inorganic hybrid coating film 13 is in the range of 50 nm to 500 nm, preferably in the range of 10 nm to 300 nm. The content of the nanobubbles 14 in the organic / inorganic hybrid coating film 13 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, more preferably in the range of 50 to 95 vol.%. 2 The total number of nano bubbles per 14 is 10 7 ~10 12 It is in the range of pieces.
[0092] The nanobubbles 14 mixed (dissolved) inside the coating liquid 10 coated to a predetermined film thickness (5 nm to 1 μm, preferably 50 nm to 500 nm) have a particle size that gradually increases from the back layer 30 (bottom) to the surface layer 28 (top) of the coating liquid 10 within the above range. Therefore, the nanobubbles 14 located in the back layer 30 (bottom) of the coating liquid 10 have the smallest particle size, the nanobubbles 14 located in the surface layer 28 (top) of the coating liquid 10 have the largest particle size, and the nanobubbles 14 located in the intermediate layer 33 (middle part) of the coating liquid 10 have a particle size intermediate between those of the nanobubbles 14 located in the back layer 30 (bottom) and the surface layer 28 (top).
[0093] As shown in an example of the structure image of the organic / inorganic hybrid coating film 13 in FIG. 4, the alkyl silicate condensate is chemically reacted with water to generate -(Si(OH) 2 -O-Si(OH) 2 It is assumed that a crosslinking reaction occurs between the hydrolysis product having a siloxane bond (Si-O-Si) and a part of the main chain in each coating layer (surface layer 28, intermediate layer 33, back layer 30) and a crosslinked structure 34 is formed, so that the organic / inorganic hybrid coating film 13 has a dense and flexible structure. In addition, the formation of the crosslinked structure 34 causes hydrophobic methyl groups (CH 3 ) and a hydrophilic hydroxyl group (OH) derived from the hydrolysis product of the alkylsilicate condensation product.
[0094] As shown in FIG. 2(c), the surface 12 of the article 11 before being coated with the organic / inorganic hybrid coating film 13 has a number of micro-level fine unevennesses 35 formed due to small scratches or the like generated during the manufacturing process or the like, unless a special surface treatment such as mirror finishing is performed. When the coating liquid 10 is coated on the surface 12 of the article 11 and hardens while penetrating the inside of the unevennesses 35, the anchor parts 36 of the organic / inorganic hybrid coating film 13 that have hardened and penetrated into the unevennesses 35 exert an anchor effect, and the organic / inorganic hybrid coating film 13 adheres more firmly to the surface 12 of the article 11. The organic / inorganic hybrid coating film 13 made from low molecular weight silane is a low molecular weight, so that it penetrates (permeates) into the entire interior area of the unevennesses 35 of the surface 12 of the article 11 as shown in FIG. 3, and hardens throughout the entire interior area of the unevennesses 35, exerting a strong anchor effect.
[0095] When the surface 12 of the article 11 is a smooth surface with almost no unevenness 35, the surface 12 of the article 11 may be roughened to form unevenness 35 with an average roughness of about 1 to 500 μm on the surface 12 of the article 11 as a pretreatment for coating with the coating liquid 10. By performing the roughening treatment in this manner, an anchor effect can be obtained by the anchor portion 36 of the organic / inorganic hybrid coating film 13. After the roughening treatment, a cleaning treatment is performed in which metal powder, plastic powder, etc. generated on the surface 12 of the article 11 is blown away using an air injection means such as an air gun. After the cleaning treatment, condensation, etc. is generated on the surface 12 of the article 11 by leaving it for a predetermined time, and naturally occurring moisture is attached to the surface 12.
[0096] In this case, after the surface 12 of the article 11 is roughened and cleaned, moisture is actively applied to the surface 12 of the article 11 on which the uneven portion 35 has been formed by roughening using a moisture applying means such as a sprayer, and then the surface 12 is coated with the coating liquid 10. In this manner, a chemical reaction between the moisture applied to the surface 12 of the article 11 and the coating liquid 10 in contact with the surface 12 of the article 11 can be promoted. Note that moisture may be applied to the surface 12 of the article 11 by a moisture applying means without performing a roughening treatment on the surface 12 of the article 11.
[0097] (Shape of the coating layer formed by the organic / inorganic hybrid coating film 13) 5, the nanobubbles 14 mixed (dissolved) inside the organic / inorganic hybrid coating film 13 formed to a predetermined film thickness (5 nm to 1 μm, preferably 50 nm to 500 nm) have a particle size that gradually increases from the back layer 30 (bottom) to the surface layer 28 (top) of the organic / inorganic hybrid coating film 13 within the above range. Therefore, the nanobubbles 14 located in the back layer 30 (bottom) of the organic / inorganic hybrid coating film 13 have the smallest particle size, the nanobubbles 14 located in the surface layer 28 (top) of the organic / inorganic hybrid coating film 13 have the largest particle size, and the nanobubbles 14 located in the intermediate layer 33 (middle part) of the organic / inorganic hybrid coating film 13 have a particle size intermediate between those of the nanobubbles 14 located at the bottom and the top.
[0098] The unevenness 35 initially formed on the surface 12 of the article 11 before being coated with the organic / inorganic hybrid coating film 13 made of polysilazane and / or siloxane is covered by the organic / inorganic hybrid coating film 13, so that the surface 12 becomes smoother after being coated with the organic / inorganic hybrid coating film 13 than before being coated with the organic / inorganic hybrid coating film 13.
[0099] FIG. 7 is a diagram showing the blend ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquid 10 of Samples A to E and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E. FIG. 8 is a diagram showing the porosity, total number of nanobubbles, and nanobubble diameter of the coating liquid 10 of Samples F to H and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples F to H. FIG. 9 is a diagram showing the blend ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquid 10 of Samples I to K and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples I to K. FIG. 10 is a diagram showing evaluations of the flexibility, impact resistance, and corrosion resistance of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to K. FIG. 11 is a diagram showing evaluations of the flexibility, impact resistance, and corrosion resistance of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples I to K.
[0100] Samples A to E were prepared in which the blending ratio of the organosilicon material (polysilazane and / or siloxane) was in the range of 30 to 60 wt%, the blending ratio of the alkyl silicate condensate was in the range of 10 to 15 wt%, and the blending ratio of the inert organic solvent was in the range of 30 to 60 wt% relative to the total mass of the coating liquid 10. Samples F to H were also prepared, each of which mainly contained low molecular weight silane. Furthermore, Samples I to K were prepared in which the blending ratio of the organosilicon material (polysilazane and / or siloxane) was in the range of 5 to 25 wt%, the blending ratio of the alkyl silicate condensate was in the range of 10 to 15 wt%, and the blending ratio of the inert organic solvent was in the range of 60 to 80 wt% relative to the total mass of the coating liquid 10.
[0101] The coating liquid 10 of Samples A to E and Samples I to K is composed of the same raw materials selected from the above-mentioned polysilazane and / or siloxane, alkyl silicate condensate, and inert organic solvent, and the content ratio of the raw materials is adjusted. Spherical nanobubbles 14 are dispersed and mixed (dispersed and dissolved) inside the coating liquid 10 of Samples A to K.
[0102] The coating liquid 10 of Sample A to Sample K was uniformly coated on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) to be coated with substantially the same thickness (5 nm to 1 μm, preferably 50 nm to 500 nm) by the above-mentioned coating (application) method, and then the surface 12 of the article 11 was left at room temperature (normal temperature) without heating to dry and harden the coating liquid 10. Alternatively, after the coating liquid 10 was coated on the surface 12 of the article 11, the surface 12 of the article 11 was irradiated with ultraviolet rays while being left at room temperature (normal temperature) to dry and harden the coating liquid 10. Alternatively, after the coating liquid 10 was coated on the surface 12 of the article 11, the surface 12 of the article 11 was irradiated with ultraviolet rays while being irradiated with infrared rays to heat the surface 12 of the article 11 to a temperature of less than 400° C. to dry and harden the coating liquid 10. In samples A to K, surface 12 of article 11 was coated with an organic / inorganic hybrid coating film 13 (glass coating layer (amorphous glass coating layer) and organic coating layer) having a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm, made from coating liquid 10.
[0103] Spherical nanobubbles 14 are dispersed (dispersed and dissolved) inside the organic / inorganic hybrid coating film 13 formed on the surface 12 of the article 11 from the coating liquid 10 of Samples A to K. Since the viscosity of the coating liquid 10 increases as the blending ratio (content) of polysilazane and / or siloxane increases, the coating liquid 10 of Samples C to D, which has a high blending ratio (content) of polysilazane and / or siloxane, may be applied in a single layer, while the coating liquid 10 of Samples A and B, which has a low blending ratio (content) of polysilazane and / or siloxane, may be applied in multiple layers, so that the surface 12 of the aluminum foil and steel plate (metal molded product) may be coated with approximately the same film thickness.
[0104] FIG. 9 shows the blending ratio of the organosilicon material (polysilazane and / or siloxane), the alkyl silicate condensate, and the inert organic solvent in the coating liquid 10 of Samples A to E, the porosity of the coating liquid 10, the total number of nanobubbles 14 mixed (dissolved) in the coating liquid 10, and the particle size of the nanobubbles 14 mixed (dissolved) in the coating liquid 10, as well as the blending ratio of the organosilicon material (polysilazane and / or siloxane), the alkyl silicate condensate, and the inert organic solvent in the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E, the porosity of the organic / inorganic hybrid coating film 13, the total number of nanobubbles 14 mixed (dissolved) in the organic / inorganic hybrid coating film 13, and the particle size of the nanobubbles 14 mixed (dissolved) in the organic / inorganic hybrid coating film 13.
[0105] FIG. 10 shows the porosity of the coating liquid 10 of Samples F to H, the total number of nanobubbles 14 mixed (dissolved) in the coating liquid 10, and the particle size of the nanobubbles 14 mixed (dissolved) in the coating liquid 10, as well as the porosity of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples F to H, the total number of nanobubbles 14 mixed (dissolved) in the organic / inorganic hybrid coating film 13, and the particle size of the nanobubbles 14 mixed (dissolved) in the organic / inorganic hybrid coating film 13.
[0106] 11 shows the blending ratio of the organic silicon material (polysilazane and / or siloxane), the alkyl silicate condensate, and the inert organic solvent in the coating liquid 10 of Sample I to Sample K, the porosity in the coating liquid 10, the total number of nanobubbles 14 mixed (dissolved) in the coating liquid 10, and the particle size of the nanobubbles 14 mixed (dissolved) in the coating liquid 10, as well as the blending ratio of the organic silicon material (polysilazane and / or siloxane), the alkyl silicate condensate, and the inert organic solvent in the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Sample I to Sample K, the porosity in the organic / inorganic hybrid coating film 13, the total number of nanobubbles 14 mixed (dissolved) in the organic / inorganic hybrid coating film 13, and the particle size of the nanobubbles 14 mixed (dissolved) in the organic / inorganic hybrid coating film 13. Samples A to K were evaluated for flexibility, impact resistance, and corrosion resistance.
[0107] (Method for evaluating the flexibility of organic / inorganic hybrid coating film 13) As a method for evaluating the flexibility of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to K, a curved surface with a radius of curvature R of about 5 mm to 10 mm was formed on a thin aluminum foil having a surface 12 covered with the organic / inorganic hybrid coating film 13, and then the state of shape change occurring in the organic / inorganic hybrid coating film 13 was visually confirmed and evaluated according to the following criteria: ◯: no cracks, △: slight cracks, ×: many cracks.
[0108] (Method for evaluating the impact resistance of organic / inorganic hybrid coating film 13) As a method for evaluating the impact resistance of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to K, a steel plate having a surface 12 covered with the organic / inorganic hybrid coating film 13 was subjected to impact under the same conditions using a DuPont impact tester, and the state of shape change occurring in the organic / inorganic hybrid coating film 13 was visually confirmed and evaluated according to the following criteria: ◯: no cracks, △: slight cracks, ×: many cracks.
[0109] (Method for evaluating the corrosion resistance of organic / inorganic hybrid coating film 13) In order to evaluate the corrosion resistance of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to K, the steel plate having the surface 12 covered with the organic / inorganic hybrid coating film 13 was placed for two months in the same environment as that in which it is exposed to flying foreign matter (in a harsh environment near a coke oven in a steelworks, exposed to coke oven gas), and the state of rust or discoloration on the surface was visually confirmed and evaluated according to the following criteria. ◯ means no rust or discoloration, and × means rust or discoloration.
[0110] The coating liquid 10 of sample A shown in FIG. 7 and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 30 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 15 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 55 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 50 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 11 pieces / 1ml(10 7 ~10 11 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed (dispersed and mixed) inside the coating liquid 10 (organic / inorganic hybrid coating film 13) in a spherical (spherical) state have a particle size of 1 nm to 500 nm.
[0111] Inside the coating liquid 10 of sample A, spherical (spherical) nanobubbles 14 with a diameter of 1 nm to 500 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed in the coating liquid 10 of sample A are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, the nanobubbles 14 do not become large bubbles in the coating liquid 10, and the nanobubbles 14 do not change into microbubbles. Furthermore, inside the organic / inorganic hybrid coating film 13 created by hardening the coating liquid 10 of sample A, spherical (spherical) nanobubbles 14 with a diameter of 1 nm to 500 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped).
[0112] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with a coating liquid 10 of sample A containing dispersed and mixed spherical (spherical) nanobubbles 14 with a particle size of 1 nm to 500 nm has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample A, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0113] The coating liquid 10 prepared as sample B and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 40 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 15 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 45 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 60 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 11 pieces / 1ml(10 7 ~10 11 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed (dispersed and mixed) inside the coating liquid 10 (organic / inorganic hybrid coating film 13) in a spherical (spherical) state have a particle size of 1 nm to 600 nm.
[0114] The nanobubbles 14 in the coating liquid 10 of sample B are dispersed and mixed (dispersed and dissolved) evenly throughout the coating liquid 10. Since the nanobubbles 14 mixed in the coating liquid 10 of sample B are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the nanobubbles 14 in the organic / inorganic hybrid coating film 14 formed by curing the coating liquid 10 of sample B are dispersed and mixed (dispersed and dissolved) evenly throughout the coating liquid 10 (trapped).
[0115] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with a coating liquid 10 of sample B containing dispersed and mixed spherical (spherical) nanobubbles 14 with a particle size of 1 nm to 600 nm has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample B, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0116] The coating liquid 10 prepared as sample C and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 50 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 13 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 37 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 70 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 12 pieces / 1ml(10 7 ~10 12 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed (dispersed and mixed) inside the coating liquid 10 (organic / inorganic hybrid coating film 13) in a spherical (spherical) state have a particle size of 50 nm to 700 nm.
[0117] Spherical (globular) nanobubbles 14 with a diameter of 50 nm to 700 nm are evenly dispersed and mixed (dispersed and dissolved) in the coating liquid 10 of sample C. Since the nanobubbles 14 mixed in the coating liquid 10 of sample C are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles in the coating liquid 10, and the nanobubbles 14 do not change into microbubbles. Moreover, spherical (globular) nanobubbles 14 with a diameter of 50 nm to 700 nm are evenly dispersed and mixed (dispersed and dissolved) in the organic / inorganic hybrid coating film 13 formed by curing the coating liquid 10 of sample C (trapped).
[0118] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with the coating liquid 10 of sample C, in which spherical (globular) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample C, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0119] The coating liquid 10 prepared as sample D and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 55 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 10 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 35 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 80 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nanobubbles per 8 ~10 12 pieces / 1ml(10 8 ~10 12 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed inside the coating liquid 10 (organic / inorganic hybrid coating film 13) in a spherical (spherical) state have a particle size of 100 nm to 800 nm.
[0120] The nanobubbles 14 in the coating liquid 10 of sample D are uniformly dispersed throughout (dispersed and dissolved). Since the nanobubbles 14 in the coating liquid 10 of sample D are negatively charged, the nanobubbles 14 do not bond with each other (coalesce), do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the nanobubbles 14 in the organic / inorganic hybrid coating film 13 formed by curing the coating liquid 10 of sample D are uniformly dispersed throughout (dispersed and dissolved) (trapped) the nanobubbles 14 in the coating liquid 10 of sample D.
[0121] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with a coating liquid 10 of sample D containing dispersed and mixed spherical (spherical) nanobubbles 14 with a particle size of 100 nm to 800 nm has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample D, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0122] The coating liquid 10 prepared as sample E and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 60 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 10 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 30 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 95 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13), 2 The total number of nano bubbles (14 per bubble) is 10 8 ~10 12 pieces / 1ml(10 8 ~10 12 pieces / 1mm 2 ) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 900 nm.
[0123] The coating liquid 10 of sample E has spherical nanobubbles 14 with a diameter of 100 nm to 900 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample E are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the organic / inorganic hybrid coating film 13 formed by curing the coating liquid 10 of sample E has spherical nanobubbles 14 with a diameter of 100 nm to 900 nm evenly dissolved and mixed (dispersed and dissolved) throughout (trapped).
[0124] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with the coating liquid 10 of sample E, in which spherical (globular) nanobubbles 14 with a particle size of 100 nm to 900 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample E, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0125] By dispersing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of Samples A to E, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating (application) amount of the coating liquid 10 itself is reduced when the coating liquid 10 of Samples A to E is coated on the surface 12 of the article 11 to be coated. In addition, by dispersing and mixing the nanobubbles 14 in the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E in which a large number of fine nanobubbles 14 are dispersed, the proportion of the organic / inorganic hybrid coating film 13 itself per unit area of the organic / inorganic hybrid coating film 13 is reduced, and the coating amount of the organic / inorganic hybrid coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.
[0126] In addition to the fact that the flexibility of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E is improved by the numerous fine nanobubbles 14 dispersed and mixed in the organic / inorganic hybrid coating film 13, the gas mixed in the organic / inorganic hybrid coating film 13 is nano-sized, so it does not affect its impact resistance or corrosion resistance. It was found that the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E has high impact resistance and high corrosion resistance despite being an ultra-thin film, and is extremely unlikely to peel or crack.
[0127] The coating liquid 10 prepared as sample F, which contains low molecular weight silane as a main component, and the organic / inorganic hybrid coating film 13 made from the coating liquid 10, have a nanobubble 14 content of 50 vol.% in the coating liquid 10 (inorganic coating film 13), and 1 mm 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 11 pieces / 1ml(10 7 ~10 11 pieces / 1mm 2 ) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 1 nm to 500 nm.
[0128] The coating liquid 10 of sample F has spherical nanobubbles 14 with a diameter of 1 nm to 500 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample F are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the organic / inorganic hybrid coating film 13 formed by hardening the coating liquid 10 of sample F has spherical nanobubbles 14 with a diameter of 1 nm to 500 nm evenly dissolved and mixed (dispersed and dissolved) throughout (trapped).
[0129] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with the coating liquid 10 of sample F, in which spherical (globular) nanobubbles 14 with a particle size of 1 nm to 500 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample F, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0130] The coating liquid 10 prepared as sample G, which contains low molecular weight silane as a main component, and the organic / inorganic hybrid coating film 13 made from the coating liquid 10, have a nanobubble 14 content of 60 vol.% in the coating liquid 10 (inorganic coating film 13) and 1 mm 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 11 pieces / 1ml(10 7 ~10 11 pieces / 1mm 2) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm.
[0131] The coating liquid 10 of sample G has spherical nanobubbles 14 with a diameter of 50 nm to 700 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample G are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the organic / inorganic hybrid coating film 13 formed by hardening the coating liquid 10 of sample G has spherical nanobubbles 14 with a diameter of 50 nm to 700 nm evenly dissolved and mixed (dispersed and dissolved) throughout (trapped).
[0132] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample G, in which spherical (globular) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample G, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0133] The coating liquid 10 prepared as sample H, which contains low molecular weight silane as a main component, and the organic / inorganic hybrid coating film 13 made from the coating liquid 10, have a nanobubble 14 content of 70 vol.% in the coating liquid 10 (inorganic coating film 13) and 1 mm 2 The total number of nano bubbles (14 per bubble) is 10 7 ~1012 pieces / 1ml(10 7 ~10 12 pieces / 1mm 2 ) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 900 nm.
[0134] The coating liquid 10 of sample H has spherical nanobubbles 14 with a diameter of 100 nm to 900 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample H are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the organic / inorganic hybrid coating film 13 formed by hardening the coating liquid 10 of sample H has spherical nanobubbles 14 with a diameter of 100 nm to 900 nm evenly dissolved and mixed (dispersed and dissolved) throughout (trapped).
[0135] An organic / inorganic hybrid coating film 13 on a surface 12 of an article 11 (aluminum foil and steel sheet (metal molded product)) made by coating with the coating liquid 10 of sample H, in which spherical (globular) nanobubbles 14 with a particle size of 100 nm to 900 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 12). It was found that by using the coating liquid 10 of sample H, an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.
[0136] By dispersing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of Samples F to H, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating amount of the coating liquid 10 itself is reduced when the coating liquid 10 of Samples F to H is coated on the surface 12 of the article 11 to be coated. In addition, by dispersing and mixing the nanobubbles 14 in the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples F to H in which a large number of fine nanobubbles 14 are dispersed, the proportion of the organic / inorganic hybrid coating film 13 itself per unit area of the organic / inorganic hybrid coating film 13 is reduced, and the coating amount of the organic / inorganic hybrid coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.
[0137] In addition to the fact that the flexibility of the organic / inorganic hybrid coating film 13 is improved by the numerous tiny nanobubbles 14 dispersed and mixed in the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples F to H, the gas mixed in the organic / inorganic hybrid coating film 13 is nano-sized, so it does not affect its impact resistance or corrosion resistance.It was found that the organic / inorganic hybrid coating films 13 made from the coating liquid 10 of Samples F to H have high impact resistance and high corrosion resistance, despite being ultra-thin films, and are extremely unlikely to peel or crack.
[0138] The coating liquid 10 prepared as sample I and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 25 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 10 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 65 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 30 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 6 ~10 8 pieces / 1ml(10 6 ~10 8 pieces / 1mm 2 ) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 900 nm.
[0139] Spherical (globular) nanobubbles 14 with a diameter of 100 nm to 900 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout the coating liquid 10 of sample I. Since the nanobubbles 14 mixed in the coating liquid 10 of sample I are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, spherical (globular) nanobubbles 14 with a diameter of 100 nm to 900 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped) within the organic / inorganic hybrid coating film 13 formed by curing the coating liquid 10 of sample I.
[0140] The coating liquid 10 prepared as sample J and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 10 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 15 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 75 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 40 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 6 ~10 9 pieces / 1ml(10 6 ~10 9 pieces / 1mm 2 ) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm.
[0141] The coating liquid 10 of sample J has spherical nanobubbles 14 with a diameter of 100 nm to 800 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed in the coating liquid 10 of sample J are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the organic / inorganic hybrid coating film 13 formed by curing the coating liquid 10 of sample J has spherical nanobubbles 14 with a diameter of 100 nm to 800 nm evenly dispersed and mixed (dispersed and dissolved) throughout (trapped).
[0142] The coating liquid 10 prepared as sample K and the organic / inorganic hybrid coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 5 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 15 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (organic / inorganic hybrid coating film 13) of 80 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 45 vol.%, and a per ml of the coating liquid 10 (1 mm of the organic / inorganic hybrid coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 10 pieces / 1ml(10 7 ~10 10 pieces / 1mm 2 ) The nanobubbles 14 dispersed and mixed inside the organic / inorganic hybrid coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm.
[0143] The coating liquid 10 of sample K has spherical nanobubbles 14 with a diameter of 50 nm to 700 nm dispersed and mixed (dispersed and dissolved) evenly throughout. Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample K are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, do not become large bubbles in the coating liquid 10, and do not change into microbubbles. Furthermore, the organic / inorganic hybrid coating film 13 formed by hardening the coating liquid 10 of sample K has spherical nanobubbles 14 with a diameter of 50 nm to 700 nm dispersed and mixed (dispersed and dissolved) evenly throughout (trapped).
[0144] By dispersing and mixing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of Samples I to K, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating amount of the coating liquid 10 itself is reduced when the coating liquid 10 of Samples I to K is coated on the surface 12 of the article 11 to be coated. In addition, by dispersing and mixing the nanobubbles 14 in the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples I to K in which a large number of fine nanobubbles 14 are dispersed and mixed, the proportion of the organic / inorganic hybrid coating film 13 itself per unit area of the organic / inorganic hybrid coating film 13 is reduced, and the coating amount of the organic / inorganic hybrid coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.
[0145] However, the organic / inorganic hybrid coating film 13 on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample I has high corrosion resistance and is rated as ◯ for corrosion resistance, but the blending ratio of the organosilicon material (polysilazane and / or siloxane) is insufficient, so its flexibility and impact resistance are poor and the flexibility and impact resistance are rated as △ (see Figure 13). It was found that even if the coating liquid 10 with the blending ratio of sample I was used, it was difficult to create an organic / inorganic hybrid coating film 13 that was excellent in all of flexibility, impact resistance, and corrosion resistance.
[0146] In addition, the organic / inorganic hybrid coating film 13 on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample J is inferior in flexibility due to the low blending ratio of the organosilicon material (polysilazane and / or siloxane), and the flexibility is evaluated as △, and the impact resistance and corrosion resistance are not recognized, and the impact resistance and corrosion resistance are evaluated as × (see FIG. 13). It was found that even if the coating liquid 10 with the blending ratio of sample J is used, it is not possible to make an organic / inorganic hybrid coating film 13 having excellent flexibility, impact resistance, and corrosion resistance.
[0147] Furthermore, the organic / inorganic hybrid coating film 13 on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample K was affected by the low blending ratio of the organosilicon material (polysilazane and / or siloxane), and its flexibility, impact resistance, and corrosion resistance were not recognized, and the evaluations of flexibility, impact resistance, and corrosion resistance were poor (see FIG. 13). It was found that even if the coating liquid 10 with the blending ratio of sample K was used, it was not possible to make an organic / inorganic hybrid coating film 13 with excellent flexibility, impact resistance, and corrosion resistance.
[0148] The organic / inorganic hybrid coating film 13 made from the coating solution 10 of samples A to H has independent ultrafine particles (average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, preferably, the average particle size D 50Since a large number of spherical nanobubbles 14 (spherical spaces) having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed (dispersed and dissolved) in the organic / inorganic hybrid coating film 13, the proportion of the organic / inorganic hybrid coating film 13 itself per unit area of the organic / inorganic hybrid coating film 13 can be reduced by the large number of ultra-fine nanobubbles 14, and the amount of the organic / inorganic hybrid coating film 13 itself coated when the surface 12 of the article 11 to be coated is reduced, making it possible to reduce the amount of the organic / inorganic hybrid coating film 13 coated on the article 11. In addition, compared to a case in which the nanobubbles 14 (spherical spaces) are not dispersed and mixed in the organic / inorganic hybrid coating film 13, the reduced amount of coating reduces the unit price of the organic / inorganic hybrid coating film 13 per unit area of the surface 12 of the article 11, and the surface 12 of the article 11 can be coated with the organic / inorganic hybrid coating film 13 at low cost.
[0149] The organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to H has a reduced mass per unit area compared to when the spherical nanobubbles 14 (spherical spaces) are not dispersed and mixed therein, and therefore when the organic / inorganic hybrid coating film 13 is used to coat the surface 12 of the article 11 to be coated, it is possible to minimize the increase in weight of the article 11 including the organic / inorganic hybrid coating film 13. For example, when the article 11 coated with the organic / inorganic hybrid coating film 13 is an automobile, it is possible to minimize the increase in weight of the automobile including the organic / inorganic hybrid coating film 13, and to prevent a decrease in fuel economy and acceleration performance of the automobile.
[0150] The organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to H has a nanobubble 14 content in the organic / inorganic hybrid coating film 13 in which the nanobubbles 14 are dispersed and mixed, in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, more preferably in the range of 50 to 90 vol.%, and the nanobubbles 14 are dispersed and mixed within 1 mm 2 The total number of nano bubbles per 14 is 10 7 ~1012 pieces / 1mm 2 Since the thickness of the organic / inorganic hybrid coating film 13 is within the range of 5 nm to 1 μm, and preferably within the range of 50 nm to 500 nm, the organic / inorganic hybrid coating film 13 does not have defects such as pinholes or slits, and can maintain corrosion resistance for a long period of time.
[0151] The organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to H has a thickness of 1 μm or less, preferably 500 nm or less, so that even if the article 11 to be coated is deformed, the organic / inorganic hybrid coating film 13 follows the deformation and can maintain the coating state of the surface 12 of the article 11 with the organic / inorganic hybrid coating film 13 for a long period of time. Even if the organic / inorganic hybrid coating film 13 contains nanobubbles 14, which are ultrafine bubbles, dispersed (dissolved), it forms a glass coating layer (amorphous glass coating layer) and an organic coating layer, so that it has excellent impact resistance and corrosion resistance, can maintain the coating state of the surface 12 of the article 11 for a long period of time, and can reliably protect the surface 12 of the article 11 with the organic / inorganic hybrid coating film 13.
[0152] The organic / inorganic hybrid coating films 13 made from the coating liquids 10 of Samples A to H exhibit excellent impact resistance and excellent corrosion resistance when their thickness is in the range of 100 nm to 1 μm, as shown in the correlation in Fig. 8. When the thickness of the organic / inorganic hybrid coating film 13 is less than 50 nm, during a chemical reaction between the coating liquid 10 and the moisture on the surface 12 of the article 11, a volatilization path for the volatilized gas is generated in a linear manner in the vertical direction of the surface 12 in the film layer, and pinholes may occur in the organic / inorganic hybrid coating film 13. However, when the thickness of the organic / inorganic hybrid coating film 13 is 50 nm to 500 nm, the volatilization path for the volatilized gas becomes a complex path, so that pinholes are not generated in the organic / inorganic hybrid coating film 13 and corrosion resistance can be maintained.
[0153] Polysilazane and / or siloxane, which are components of the organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E, contain methyl groups (CH 3 ) content of 50% or more, the hydrophobic methyl group (CH 3 Since the water contact angle on the surface of the organic / inorganic hybrid coating film 13 is large, moisture and foreign matter are less likely to adhere to the organic / inorganic hybrid coating film 13, and the organic / inorganic hybrid coating film 13 has high water repellency and high antifouling effect. This organic / inorganic hybrid coating film 13 has a structure in which many hydrophobic methyl groups (CH 3 ) and hydrophilic hydroxyl groups (OH) derived from the hydrolysis products of alkyl silicate condensates are mixed and coordinated, thereby improving the drainage properties on the surface of the organic / inorganic hybrid coating film 13 and providing a high antifouling effect.
[0154] The organic / inorganic hybrid coating film 13 made from the coating liquid 10 of Samples A to E is formed on a smooth surface with nano-level minute unevenness 37 (dimples) formed on the surface, which makes it difficult for moisture or foreign matter to adhere to the surface of the organic / inorganic hybrid coating film 13, and has high water repellency and high antifouling effect. In addition, since the condensation reaction of polysilazane and / or siloxane occurs rapidly, the time required to form the organic / inorganic hybrid coating film 13 using the coating liquid 10 can be shortened. [Explanation of symbols]
[0155] 10 Coating liquid 11 Goods 12 Surface 13 Organic / inorganic hybrid coating film 14 Nanobubbles 15 Nanobubble mixing device 16 Coating liquid storage tank 17 Gas supply tank 18 Water Pump 19 Air supply pump 20 Static fluid mixer (nanobubble generator) 21 Coating liquid storage tank 22 Water supply pipeline 23 Air supply line 24 Mixing line 25 Supply pipeline 26 Cylinder Unit 27 Moisture 28 Surface layer 29 Covering layer 30 back layer 31 Covering layer 32 Covering layer 33 Middle Class 34 Crosslinked structure 35 Uneven part 36 Anchor section
Claims
1. An organic / inorganic hybrid coating film that contains a glass component in a hardened state and that coats the surface of an article to be coated, The organic / inorganic hybrid coating film is characterized in that a large number of independent fine spherical spaces are dispersed and mixed inside the organic / inorganic hybrid coating film.
2. The spherical space is formed by nanobubbles, and the average particle diameter D of the nanobubbles 90 is less than 1 μm, and the average particle size D 90 2. The organic / inorganic hybrid coating film according to claim 1, wherein the nanobubbles are dispersed and mixed in the organic / inorganic hybrid coating film at a predetermined concentration.
3. The average particle size D of the nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and the average particle size D 50 3. The organic / inorganic hybrid coating film according to claim 2, wherein the nanobubbles are dispersed and mixed in the organic / inorganic hybrid coating film at a predetermined concentration.
4. 4. The organic / inorganic hybrid coating film according to claim 3, wherein the content of the nanobubbles in the organic / inorganic hybrid coating film is in the range of 10 to 95 vol. %.
5. The organic / inorganic hybrid coating film according to claim 4, wherein the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them.
6. A coating solution for forming an organic / inorganic hybrid coating film containing a glass component in a hardened state on the surface of an article to be coated, comprising: The coating liquid is produced by mixing a liquid silicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent in a predetermined mixing ratio, or the coating liquid is mainly composed of low molecular weight silane, and a large number of independent fine spherical spaces are dispersed and mixed inside the coating liquid consisting of the silicon material, the alkyl silicate condensate, and an inert organic solvent, or inside the coating liquid consisting mainly of low molecular weight silane.
7. The spherical space is formed by nanobubbles, and the average particle diameter D of the nanobubbles 90 is less than 1 μm, and the average particle size D 90 The coating liquid according to claim 6, wherein the nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.
8. The average particle size D of the nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and the average particle size D 50 The coating liquid according to claim 7, wherein the nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.
9. 9. The coating liquid according to claim 8, wherein the content of the nanobubbles in the coating liquid is in the range of 10 to 95 vol. %.
10. 10. The coating liquid according to claim 9, wherein the blending ratio of the silicon material to the total mass of the coating liquid before the nanobubbles are mixed therein is in the range of 30 to 60 wt %, the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid before the nanobubbles are mixed therein is in the range of 10 to 15 wt %, the blending ratio of the inert organic solvent to the total mass of the coating liquid before the nanobubbles are mixed therein is in the range of 30 to 60 wt %, the viscosity of the coating liquid at 20° C. into which the nanobubbles are dispersed and mixed is in the range of 0.98 to 1.008 mPa s, and the rising speed of the nanobubbles in the coating liquid at 20° C. into which the nanobubbles are dispersed and mixed is in the range of 0.000015 to 0.00005 mm / min.
11. 11. The coating liquid according to claim 10, wherein the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them.
Citation Information
Patent Citations
Coating liquid and coating method
JP2021014514A
